Non-aqueous lithium electricity storage element
By using activated carbon and carbon materials as positive and negative electrode active materials in non-aqueous lithium power storage components, and optimizing electrolyte and process processing, the durability problem of existing lithium-ion batteries and electric double layer capacitors under high temperature cycle conditions is solved, and high energy density and high output characteristics are achieved.
Patent Information
- Application Number
- CN202380064271.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-08
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-15
AI Technical Summary
Existing lithium-ion batteries and electric double-layer capacitors have durability problems under high temperature cycle conditions, making it difficult to take into account high energy density and high output characteristics.
Non-aqueous lithium power storage elements are used, and the positive electrode is activated carbon and alkali metal compounds are used, and the negative electrode is carbon material is used, and the structure and composition of the positive electrode and negative electrode active material layers are optimized through specific electrolytes and processes.
It realizes a non-aqueous lithium power storage element with high high-temperature cycle durability, which has high energy density and high output characteristics, and does not require restriction of discharge depth.
Smart Images

Figure CN119836671A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a non-aqueous lithium storage element. This international application claims priority based on Japanese Patent Application No. 2022-143057 filed on September 8, 2022, the entire contents of which are incorporated herein by reference. Background Art
[0002] In recent years, from the perspective of effectively utilizing energy in order to protect the earth's environment and save resources, wind power generation power stabilization systems, late-night power storage systems, household distributed power storage systems based on solar power generation technology, and power storage systems for electric vehicles have attracted attention. The first requirement for batteries used in these power storage systems is high energy density. As a powerful supplement to high-energy density batteries that can meet such requirements, the development of lithium-ion batteries has been actively promoted. The second requirement is high output characteristics. For example, in the combination of a high-efficiency engine and a power storage system (such as a hybrid electric vehicle), or a combination of a fuel cell and a power storage system (such as a fuel cell electric vehicle), the power storage system is required to have high output discharge characteristics during acceleration. At present, double-layer capacitors, nickel-metal hydride batteries, etc. are being developed as high-output power storage devices.
[0003] Among double-layer capacitors, the double-layer capacitor using activated carbon as the electrode has an output characteristic of about 0.5 to 1kW / L. This double-layer capacitor not only has high output characteristics, but also has high durability (cycle characteristics and high-temperature storage characteristics), and is considered to be the best device in the above-mentioned field requiring high output. However, its energy density is only about 1 to 5Wh / L, so it is necessary to further improve the energy density. On the other hand, the nickel-hydrogen battery commonly used in hybrid electric vehicles has a high output equivalent to that of double-layer capacitors, and has an energy density of about 160Wh / L. However, there are problems with durability (especially stability at high temperatures), and research is being actively carried out to further improve energy density and output characteristics, and to improve durability.
[0004] In addition, in lithium-ion batteries, research has also been conducted towards high output. For example, a lithium-ion battery with a high output of more than 3kW / L has been developed when the depth of discharge (i.e., the ratio of the discharge amount to the discharge capacity of the storage element (%)) is 50%. However, its energy density is less than 100Wh / L, and the high energy density, which is the biggest feature of lithium-ion batteries, is deliberately suppressed by the design. In addition, its durability (cycle characteristics and high-temperature storage characteristics) is inferior to that of double-layer capacitors. Therefore, for such lithium-ion batteries, in order to make them have practical durability, they are used in a range narrower than the range of 0 to 100% of the depth of discharge. Since the capacity of lithium-ion batteries that can be actually used will be further reduced, research is actively conducted to further improve durability.
[0005] As a powerful supplement to storage devices that can achieve both high energy density and high output characteristics, storage elements called lithium ion capacitors have attracted attention and are being actively developed. Lithium ion capacitors are a type of storage element that uses a non-aqueous electrolyte containing lithium salts (hereinafter also referred to as "non-aqueous lithium storage element"), and are storage elements that charge and discharge by performing a non-Faraday reaction based on the adsorption and desorption of anions at the positive electrode at about 3V or more, similar to double-layer capacitors, and a Faradaic reaction based on the absorption and release of lithium ions at the negative electrode, similar to lithium ion batteries.
[0006] The characteristic of lithium-ion capacitors is that activated carbon (1 times the energy density) is used at the positive electrode, and carbon material (10 times the energy density) is used at the negative electrode. The charging and discharging is performed by performing a non-Faraday reaction at the positive electrode and a Faradaic reaction at the negative electrode. Therefore, it is an asymmetric capacitor that has the characteristics of both double-layer capacitors and lithium-ion secondary batteries. Lithium-ion capacitors have the following characteristics: while having high output and high durability, they have high energy density (1 times the positive electrode × 10 times the negative electrode = 10), and there is no need to limit the discharge depth like lithium-ion secondary batteries.
[0007] Various studies have been conducted on further improving the durability of the above-mentioned lithium ion capacitors (see Patent Documents 1 to 3 below). For example, Patent Document 1 describes a positive electrode for a non-aqueous electrolyte secondary battery, wherein, in at least one electron microscope image of a cross section of a positive electrode for a non-aqueous electrolyte secondary battery taken with an electron microscope without a binder, the cross section of the connecting portion includes a large porosity region and a small porosity region (the small porosity region is arranged along the surface of the positive electrode active material body, and the porosity is smaller than the porosity of the large porosity region).
[0008] Patent document 2 describes a non-aqueous lithium storage element, in which, in a binary image of a SEM image taken of the surface of a negative electrode active material layer, when the set of maximum inscribed circles enclosing each pixel is represented in the form of a frequency distribution of each diameter for all pixels in the bright field area, the area ratio Z1 of the total area of the largest inscribed circles with a diameter less than 100 nm in the total area of the largest inscribed circles is greater than 3.5% and less than 25.5%.
[0009] Patent document 3 describes a negative electrode for a non-aqueous electrolyte secondary battery, wherein 15 surface SEM images obtained from different positions on the negative electrode surface are randomly selected, and each image is divided into a particle area and an inter-particle gap area. The inter-particle gap area is calculated from the processed image obtained by binarizing each image, and the standard deviation of the fractal dimension of the inter-particle gap area calculated by the box counting method is less than 0.1.
[0010] It should be noted that in the present disclosure, the mesopore volume is calculated by the BJH method, and the micropore volume is calculated by the MP method. The BJH method is proposed in non-patent document 1, and the MP method refers to a method for calculating the micropore volume, micropore area and micropore distribution using the "t-plot method" (non-patent document 2), and the MP method is shown in non-patent document 3.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: International Publication No. 2019 / 244282
[0014] Patent Document 2: International Publication No. 2021 / 066174
[0015] Patent Document 3: Japanese Patent Application Publication No. 2021-158088
[0016] Non-patent literature
[0017] Non-patent document 1: EP Barrett, LG Joyner and P. Halenda, "The Determination of Pore Volume and Area Distributions in Porous Substances", J. Am. Chem. Soc., (1951), 73, pp. 373-380
[0018] Non-patent document 2: BC Lippens and JH de Boer, "Studies on pore systems in Catalysis V. The t Method", J. Catalysis, (1965), 4, pp. 319-323
[0019] Non-patent document 3: RSMikhail, S. Brunauer and EEBodor, "Investigations of a Complete Pore Structure Analysis", J. Colloid Interface Sci., (1968), 26, pp. 45-53 Summary of the invention
[0020] Problems to be solved by the invention
[0021] One of the objects of the present disclosure is to provide a non-aqueous lithium storage element having high high-temperature cycle durability.
[0022] Means for solving problems
[0023] Examples of embodiments of the present disclosure are listed in the following items [1] to
[10] . [1]
[0025] A non-aqueous lithium storage element comprises a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte containing lithium ions, wherein the positive electrode comprises a positive electrode active material layer containing a positive electrode active material and an alkali metal compound, wherein:
[0026] Regarding the above-mentioned negative electrode, a secondary electron image of the surface of the negative electrode active material layer obtained by taking it at a magnification of 100 times using a scanning electron microscope without exposure to the atmosphere is binarized with the brightness of each pixel. In the image obtained by binarization, there are bright field areas and a plurality of dark field areas, and the plurality of dark field areas correspond to deposits formed on the surface of the above-mentioned negative electrode active material layer. When 1 pixel is set to 1.46μm, the maximum value S [pixel] of the area occupied by each of the above-mentioned dark field areas 2 ] is less than 4000. [2]
[0028] The non-aqueous lithium storage element as described in [1], wherein the positive electrode active material is activated carbon, the alkali metal compound is lithium carbonate, and the non-aqueous electrolyte comprises an electrolyte salt containing lithium ions and a cyclic compound selected from cyclic carbonates and cyclic sulfates. [3]
[0030] The non-aqueous lithium storage element as described in [1] or [2], wherein the maximum value S of the area of the dark field region is 3500 [pixels 2 ]the following. [4]
[0032] The nonaqueous lithium storage element according to any one of [1] to [3], wherein the maximum value S of the area of the dark field region is 2408 [pixels 2 ] or more, 3000[pixels 2 ]the following. [5]
[0034] The nonaqueous lithium storage element according to [4], wherein the nonaqueous electrolyte solution contains the cyclic sulfate ester, and the cyclic sulfate ester is vinyl sulfate. [6]
[0036] The nonaqueous lithium storage element according to any one of [1] to [5], wherein the deposit corresponding to the dark field region of the binary image of the surface of the negative electrode active material contains a compound derived from metal Li. [7]
[0038] The nonaqueous lithium storage element according to any one of [1] to [6], wherein the amount of lithium ions doped in the negative electrode is 85% or more and 100% or less. [8]
[0040] The nonaqueous lithium storage element as described in any one of [1] to [7], wherein in the binarized image, when 1 pixel is set to 1.46 μm, the average value T [pixel] of the area occupied by each of the dark field regions is 2 ] is below 600. [9]
[0042] The nonaqueous lithium storage element according to [8], wherein the average value T is 400 or less.
[10]
[0044] A method for manufacturing a non-aqueous lithium storage element, wherein the method comprises the following steps:
[0045] A first doping step, charging a non-aqueous lithium storage element at 0.05C to 0.20C until it reaches 4.1 to 4.3V, wherein the non-aqueous lithium storage element comprises a positive electrode precursor, a negative electrode, a separator, and a non-aqueous electrolyte, wherein the positive electrode precursor comprises a positive electrode active material layer comprising a positive electrode active material and lithium carbonate, wherein the positive electrode active material comprises activated carbon, and the non-aqueous electrolyte comprises an electrolyte salt containing lithium ions and a cyclic compound selected from cyclic carbonates and cyclic sulfates; and
[0046] In the second doping step, the nonaqueous lithium storage element is then charged at 0.25C to 1.0C until the voltage reaches 4.4 to 4.6V.
[0047] Effects of the Invention
[0048] According to the present disclosure, a non-aqueous lithium storage element having high high-temperature cycle durability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a secondary electron image (SEM image) obtained by photographing the surface of the negative electrode active material layer of Example 1 at a magnification of 100 times using a scanning electron microscope without being exposed to the atmosphere.
[0050] Figure 2 is for Figure 1 The secondary electron image is obtained by binarizing the brightness of each pixel.
[0051] Figure 3 This is a secondary electron image (SEM image) obtained by photographing the surface of the negative electrode active material layer of Comparative Example 1 at a magnification of 100 times using a scanning electron microscope without being exposed to the atmosphere.
[0052] Figure 4 is for Figure 3 The secondary electron image is obtained by binarizing the brightness of each pixel. DETAILED DESCRIPTION
[0053] The embodiments of the present disclosure are described in detail below, but the present disclosure is not limited to the following embodiments. The upper limit and the lower limit in each numerical range of the following embodiments can be arbitrarily combined to form an arbitrary numerical range.
[0054] 《Non-aqueous lithium battery elements》
[0055] A non-aqueous lithium storage element generally has a positive electrode, a negative electrode, a separator, and an electrolyte as main components. As the electrolyte, a solution in which alkali metal ions are dissolved in an organic solvent (hereinafter also referred to as a "non-aqueous electrolyte") is used.
[0056] <Positive Electrode and Positive Electrode Precursor>
[0057] The positive electrode and the positive electrode precursor in the present disclosure have a positive electrode current collector and a positive electrode active material layer containing a positive electrode active material disposed thereon (more specifically, provided on one or both sides thereof). The positive electrode active material preferably contains a carbon material (preferably activated carbon) and may contain an alkali metal compound as needed. As described below, in the present disclosure, in the step of assembling the power storage element, it is preferred to pre-dope alkali metal ions in the negative electrode. As the pre-doping method, it is preferred to apply a voltage between the positive electrode precursor and the negative electrode after assembling the power storage element using a positive electrode precursor containing an alkali metal compound, a negative electrode, a separator, an outer package, and a non-aqueous electrolyte. The alkali metal compound can be contained in the positive electrode precursor in any manner. For example, the alkali metal compound may be present between the positive electrode current collector and the positive electrode active material layer or on the surface of the positive electrode active material layer. The alkali metal compound is preferably contained in the positive electrode active material layer formed on the positive electrode current collector of the positive electrode precursor. In this specification, the positive electrode before the alkali metal doping step is defined as the "positive electrode precursor", and the positive electrode after the alkali metal doping step is defined as the "positive electrode".
[0058] [Positive electrode active material layer]
[0059] The positive electrode active material layer contains a positive electrode active material and an alkali metal compound. In the positive electrode active material layer, in addition to these components, optional components described later may be contained as needed.
[0060] [Positive electrode active material]
[0061] The positive electrode active material preferably contains activated carbon. In the positive electrode active material, in addition to activated carbon, carbon nanotubes, graphene, conductive polymers, lithium transition metal oxides, etc. may be further contained. As the lithium transition metal oxide, known materials used in lithium ion batteries can be used.
[0062] When using activated carbon as the positive electrode active material, there are no particular restrictions on the type and raw material of the activated carbon. In order to balance high input-output characteristics and high energy density, it is preferred to optimally control the pores of the activated carbon. Specifically, when the mesopore volume of pores with a diameter or more calculated by the BJH method is set as V1 (cc / g) and the micropore volume of pores with a diameter less than calculated by the MP method is set as V2 (cc / g), (1) in order to obtain high input-output characteristics, it is preferred to satisfy 0.3 < V1 ≤ 0.8 and 0.5 ≤ V2 ≤ 1.0, and the specific surface area measured by the BET method is 1,500 m 2 / g or more and 3,000 m 2Activated carbon with a specific surface area of less than 2,300 m² / g (hereinafter also referred to as activated carbon 1). In addition, (2) in order to obtain a high energy density, it is preferably satisfied that 0.8 < V1 ≤ 2.5 and 0.8 < V2 ≤ 3.0, and the specific surface area measured by the BET method is 2,300 m² / g 2 / g or more and 4,000 m² / g 2 / g or less of activated carbon (hereinafter also referred to as activated carbon 2).
[0063] The BET specific surface area, mesopore volume, micropore volume, and average pore diameter of the active material in the present disclosure are the values obtained by the following methods. The sample is vacuum dried at 200 °C for one day and night, and nitrogen is used as the adsorbed substance to measure the adsorption-desorption isotherm. Using the adsorption-side isotherm obtained here, the BET specific surface area is calculated by the BET multi-point method or the BET single-point method, the mesopore volume is calculated by the BJH method, and the micropore volume is calculated by the MP method. The BJH method is a calculation method commonly used in the analysis of mesopores and is a method proposed by Barrett, Joyner, Halenda, etc. (Non-Patent Document 1). In addition, the MP method refers to a method of obtaining the micropore volume, micropore area, and micropore distribution by using the "t-plot method" (Non-Patent Document 2) and is a method designed by R.S. Mikhail, Brunauer, and Bodor (Non-Patent Document 3). In addition, the average pore diameter refers to the value obtained by measuring the equilibrium adsorption amount of nitrogen at each relative pressure at liquid nitrogen temperature and dividing the total pore volume per unit mass of the sample by the above BET specific surface area.
[0064] (Activated carbon 1)
[0065] From the perspective of increasing the input-output characteristics after assembling the positive electrode material into the storage element, the mesopore volume V1 of the activated carbon 1 is preferably greater than 0.3cc / g. From the perspective of suppressing the reduction of the stacking density of the positive electrode, V1 is preferably less than 0.8cc / g. V1 is more preferably 0.35cc / g or more and 0.7cc / g or less, and further preferably 0.4cc / g or more and 0.6cc / g or less. In order to increase the specific surface area and capacity of the activated carbon, the micropore volume V2 of the activated carbon 1 is preferably 0.5cc / g or more. From the perspective of suppressing the volume of the activated carbon, increasing the density as an electrode, and increasing the capacity per unit volume, V2 is preferably less than 1.0cc / g. V2 is more preferably 0.6cc / g or more and 1.0cc / g or less, and further preferably 0.8cc / g or more and 1.0cc / g or less. The ratio of the mesopore volume V1 to the micropore volume V2 (V1 / V2) is preferably in the range of 0.3≤V1 / V2≤0.9. That is, from the perspective of increasing the ratio of the amount of mesopores to the amount of micropores to the amount of micropores to the amount of mesopores to the extent that the decrease in output characteristics can be suppressed while maintaining high capacity, V1 / V2 is preferably 0.3 or more. On the other hand, from the perspective of increasing the ratio of the amount of micropores to the amount of mesopores to the extent that the decrease in capacity can be suppressed while maintaining high output characteristics, V1 / V2 is preferably 0.9 or less. A more preferred range of V1 / V2 is 0.4≤V1 / V2≤0.7, and a further preferred range of V1 / V2 is 0.55≤V1 / V2≤0.7.
[0066] From the viewpoint of maximizing the output of the obtained electric storage element, the average pore diameter of the activated carbon 1 is preferably More preferably Above, most preferably In addition, from the perspective of maximizing the capacity, the average pore size of the activated carbon 1 is preferably The BET specific surface area of the activated carbon 1 is preferably 1,500 m 2 / g above 3,000m 2 / g or less, more preferably 1,500m 2 / g or more 2,500m 2 / g or less. BET specific surface area is 1,500m 2 / g or more, a good energy density is easily obtained, while a BET specific surface area of 3,000 m 2 When the amount of the binder is 0.1477 W / g or less, there is no need to add a large amount of binder to ensure the strength of the electrode, so the performance per unit volume of the electrode is improved.
[0067] Activated carbon 1 having the above-mentioned characteristics can be obtained, for example, using the raw materials and treatment methods described below. There is no particular limitation on the carbon source used as the raw material of activated carbon 1. For example, plant raw materials such as wood, wood powder, coconut shells, by-products of pulp production, bagasse, and waste molasses can be cited; fossil raw materials such as peat, charcoal, lignite, bituminous coal, anthracite, petroleum distillation residue components, petroleum asphalt, coke, and coal tar; phenol resins, vinyl chloride resins, vinyl acetate resins, melamine resins, urea resins, resorcinol resins, celluloid, epoxy resins, polyurethane resins, polyester resins, polyamide resins and other synthetic resins; synthetic rubbers such as polybutene, polybutadiene, and polychloroprene; other synthetic woods, synthetic pulps, and the like, and their carbonized products. Among these raw materials, plant raw materials such as coconut shells and wood powder and their carbonized products are preferred from the perspective of mass production and cost, and coconut shell carbonized products are particularly preferred.
[0068] As a method for carbonizing and activating these raw materials into the above-mentioned activated carbon 1, known methods such as fixed bed method, moving bed method, fluidized bed method, slurry method, rotary kiln method, etc. can be used. As a carbonization method for these raw materials, inert gases such as nitrogen, carbon dioxide, helium, argon, xenon, neon, carbon monoxide, combustion exhaust gas, etc. can be cited, or a gas with these inert gases as the main component and mixed with other gases can be used, preferably at a temperature of 400°C to 700°C, more preferably 450°C to 600°C, for 30 minutes or more and 10 hours or less. As an activation method for the carbide obtained by the carbonization method described above, it is preferred to use a gas activation method using water vapor, carbon dioxide, oxygen and other activated gases for firing. Among these, a method using water vapor or carbon dioxide as an activated gas is preferred. In the activation method, the activation gas is preferably supplied at a ratio of preferably 0.5 kg / h to 3.0 kg / h, more preferably 0.7 kg / h to 2.0 kg / h, and the obtained carbide is preferably heated to 800°C to 1,000°C for 3 to 12 hours, more preferably 5 to 11 hours, and further preferably 6 to 10 hours for activation. Furthermore, before the activation treatment of the carbide described above, the carbide can be activated once in advance. In this activation, the following method can usually be preferably used: using an activation gas such as water vapor, carbon dioxide, oxygen, etc., the carbon material is fired at a temperature below 900°C to perform gas activation.
[0069] The activated carbon 1 that can be used in the present disclosure can be produced by appropriately combining the firing temperature and firing time in the carbonization method described above with the activation gas supply amount, temperature increase rate, and maximum activation temperature in the activation method.
[0070] The average particle size of activated carbon 1 is preferably 2 μm to 20 μm, more preferably 2 μm to 15 μm, and further preferably 3 μm to 10 μm. When the average particle size is 2 μm or more, the capacity per unit volume of the electrode tends to increase due to the high density of the active material layer. It should be noted that if the average particle size is small, it may lead to disadvantages such as low durability, but if the average particle size is 2 μm or more, it is not easy to produce such disadvantages. On the other hand, if the average particle size is 20 μm or less, it tends to be easily suitable for high-speed charging and discharging.
[0071] (Activated carbon 2)
[0072] From the perspective of increasing the output characteristics after assembling the positive electrode material into the storage element, the mesopore volume V1 of the activated carbon 2 is preferably greater than 0.8cc / g. From the perspective of suppressing the reduction in the capacity of the storage element, V1 is preferably less than 2.5cc / g. V1 is more preferably 1.00cc / g or more and 2.0cc / g or less, and further preferably 1.2cc / g or more and 1.8cc / g or less. In order to increase the specific surface area of the activated carbon and increase the capacity, the micropore volume V2 of the activated carbon 2 is preferably greater than 0.8cc / g. From the perspective of increasing the density of the activated carbon as an electrode and increasing the capacity per unit volume, V2 is preferably less than 3.0cc / g. V2 is more preferably greater than 1.0cc / g and less than 2.5cc / g, and further preferably 1.5cc / g or more and less than 2.5cc / g. Compared with the existing activated carbon used for double-layer capacitors or lithium-ion capacitors, the BET specific surface area of the activated carbon 2 having the above-mentioned mesopore volume and micropore volume is higher. The specific value of the BET specific surface area of the activated carbon 2 is preferably 2,300 m 2 / g above 4,000m 2 / g or less, more preferably 3,000m 2 / g above 4,000m 2 / g or less, more preferably 3,200m 2 / g above 3,800m 2 / g or less. BET specific surface area is 2,300m 2 / g or more, it is easy to obtain a good energy density, and the BET specific surface area is 4,000m 2 When the electrode thickness is 0.1477 W / g or less, it is not necessary to add a large amount of binder to ensure the electrode strength, so the performance per unit volume of the electrode is improved.
[0073] The activated carbon 2 having the above-mentioned characteristics can be obtained, for example, using the raw materials and treatment methods described below. The carbonaceous material used as the raw material of the activated carbon 2 is not particularly limited as long as it is a carbon source commonly used as an activated carbon raw material. For example, plant raw materials such as wood, wood powder, and coconut shells; fossil raw materials such as petroleum asphalt and coke; various synthetic resins such as phenol resin, furan resin, vinyl chloride resin, vinyl acetate resin, melamine resin, urea resin, and resorcinol resin can be cited. Among these raw materials, phenol resin and furan resin are suitable for making activated carbon with a high specific surface area and are particularly preferred.
[0074] As a method of carbonizing these raw materials or a heating method during activation treatment, for example, known methods such as a fixed bed method, a moving bed method, a fluidized bed method, a slurry method, and a rotary kiln method can be cited. The atmosphere during heating uses an inert gas such as nitrogen, carbon dioxide, helium, and argon, or uses a gas composed mainly of these inert gases and mixed with other gases. It is usually a method of firing for about 0.5 hours or more and about 10 hours or less at a carbonization temperature of about 400°C to 700°C. As a method for activating carbides, there are gas activation methods using activation gases such as water vapor, carbon dioxide, and oxygen for firing; and alkali metal activation methods for heating treatment after mixing with alkali metal compounds. In order to make activated carbon with a high specific surface area, alkali metal activation methods are preferred. In this activation method, carbides can be mixed with alkali metal compounds such as KOH and NaOH in a mass ratio of 1:1 or more (the amount of alkali metal compounds is the same as the amount of carbides or is more than the amount of carbides). After mixing, heating can be performed at a temperature in the range of 600°C to 900°C under an inert gas atmosphere for 0.5 hours to 5 hours. After heating, the alkali metal compound can be removed by washing with acid and water, and further dried. In order to increase the amount of micropores without increasing the amount of mesopores, the amount of carbides can be increased during activation to mix with KOH. In order to increase both the amount of micropores and the amount of mesopores, the amount of KOH can be increased for use. In addition, in order to mainly increase the amount of mesopores, it is preferred to perform water vapor activation after performing alkali activation treatment.
[0075] The average particle size of the activated carbon 2 is preferably 2 μm or more and 20 μm or less, and more preferably 3 μm or more and 10 μm or less.
[0076] (How to use activated carbon)
[0077] Activated carbon 1 and activated carbon 2 may be one type of activated carbon respectively, or may be a mixture of more than two types of activated carbon and the above-mentioned characteristic values are displayed as a whole mixture. Activated carbon 1 and activated carbon 2 may select any one of them for use, or may mix the two for use. The positive electrode active material may also include materials other than activated carbon 1 and activated carbon 2 (e.g., activated carbon not having the specific V1 and / or V2 described above, or materials other than activated carbon (e.g., conductive polymers, etc.)). Based on the total mass of the positive electrode active material layer, the total content of activated carbon 1 and activated carbon 2 in the positive electrode active material layer of the positive electrode precursor is preferably 40.0 mass % or more and 70.0 mass % or less, more preferably 45.0 mass % or more and 65.0 mass % or less. When the value is 40.0 mass % or more, the energy density can be improved. When the value is 70.0 mass % or less, the high temperature durability and high voltage durability can be improved.
[0078] (Lithium Transition Metal Oxide)
[0079] The positive electrode active material may further include a lithium transition metal compound. By including a lithium transition metal oxide, the non-aqueous lithium storage element can be made high-capacity. The lithium transition metal oxide includes a transition metal oxide that can absorb and release lithium. There is no particular limitation on the transition metal oxide used as the positive electrode active material. As the transition metal oxide, for example, an oxide containing at least one element selected from the group consisting of cobalt, nickel, manganese, iron, vanadium and chromium can be cited. As the transition metal oxide, specifically, a compound represented by the following formula can be cited:
[0080] Li x CoO2{where x satisfies 0≤x≤1},
[0081] Li x NiO2{where x satisfies 0≤x≤1},
[0082] Li x Ni y M (1-y) O2{wherein, M is at least one element selected from the group consisting of Co, Mn, Al, Fe, Mg and Ti, x satisfies 0≤x≤1, and y satisfies 0.05 <y<0.97}、
[0083] Li x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2{where x satisfies 0≤x≤1},
[0084] Li x MnO2{where x satisfies 0≤x≤1},
[0085] α-Li x FeO2 {where x satisfies 0 ≤ x ≤ 1},
[0086] Li x VO2 {where x satisfies 0 ≤ x ≤ 1},
[0087] Li x CrO2 {where x satisfies 0 ≤ x ≤ 1},
[0088] Li x FePO4 {where x satisfies 0 ≤ x ≤ 1},
[0089] Li x MnPO4 {where x satisfies 0 ≤ x ≤ 1},
[0090] Li z V2(PO4)3 {where z satisfies 0 ≤ z ≤ 3},
[0091] Li x Mn2O4 {where x satisfies 0 ≤ x ≤ 1},
[0092] Li x M y Mn (2-y) O4 {where M is at least one element selected from the group consisting of Co, Mn, Al, Fe, Mg, and Ti, x satisfies 0 ≤ x ≤ 1, and y satisfies 0.05 < y < 0.97},
[0093] Li x Ni a Co b Al (1-a-b) O2 {where x satisfies 0 ≤ x ≤ 1, and a and b satisfy 0.02 < a < 0.97 and 0.02 < b < 0.97},
[0094] Li x Ni c Co d Mn (1-c-d) O2 {where x satisfies 0 ≤ x ≤ 1, and c and d satisfy 0.02 < c < 0.97 and 0.02 < d < 0.97}, etc.
[0095] From the aspects of high capacity, low resistance, cycle characteristics, decomposition of alkali metal compounds different from the positive electrode active material, and suppression of shedding of the positive electrode active material during pre-doping, among these, the transition metal oxide used as the positive electrode active material is preferably the above formula Li x Ni a Co b Al (1-a-b) O2, Li x Ni cCo d Mn (1-c-d) O2、Li x CoO2、Li x Mn2O4, or Li x FePO4、Li x MnPO4 and Li z A compound represented by V2(PO4)3.
[0096] If an alkali metal compound different from the positive electrode active material is included in the positive electrode, the alkali metal compound can be pre-doped into the negative electrode as a dopant source of the alkali metal during pre-doping, so even if lithium ions are not pre-included in the transition metal compound (that is, even if x=0 or z=0), it can be electrochemically charged and discharged as a non-aqueous lithium storage element. Based on the total mass of the positive electrode active material layer, the content of lithium transition metal oxide in the positive electrode active material layer of the positive electrode precursor is preferably 8.0 mass% or more and 30.0 mass% or less. If the content of lithium transition metal oxide is 8.0 mass% or more, the non-aqueous lithium storage element can be made high-capacity. When the content of lithium transition metal oxide is 30.0 mass% or less, the non-aqueous lithium storage element can be made low-resistance.
[0097] [Alkali metal compounds]
[0098] The positive electrode active material layer of the positive electrode and positive electrode precursor disclosed in the present invention contains an alkali metal compound. In the case where the positive electrode active material layer contains an alkali metal compound as a positive electrode active material, the positive electrode active material layer further contains an alkali metal compound other than the positive electrode active material. As such an alkali metal compound, for example, an oxide such as M2O in which M is one or more selected from Li, Na, K, Rb, and Cs; a hydroxide such as MOH; a halide such as MF, MCl; a carboxylate such as RCOOM (where R is H, an alkyl group, or an aryl group), and one or more of them can be used. As an alkali metal compound, specifically, for example, lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, cesium carbonate, lithium oxide, lithium hydroxide, and the like can be cited. As an alkali metal compound, it is suitable to use one or more alkali metal carbonates selected from lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, and cesium carbonate, and it is more suitable to use lithium carbonate, sodium carbonate, or potassium carbonate. From the aspect of high capacity per unit mass, lithium carbonate is particularly suitable.
[0099] The positive electrode active material layer of the positive electrode and the positive electrode precursor may contain at least one alkali metal compound in addition to the positive electrode active material. The positive electrode and the positive electrode precursor may contain the above-mentioned alkali metal compound and at least one selected from carbonates, oxides, hydroxides, halides and carboxylates of an alkaline earth metal selected from the group consisting of Be, Mg, Ca, Sr and Ba.
[0100] The alkali metal compound and the alkaline earth metal compound in the case of using an alkaline earth metal compound are preferably in a microparticle form. In the present disclosure, the average particle size of the alkali metal compound present in the positive electrode active material layer of the positive electrode precursor is preferably 0.1 μm or more and 10 μm or less. If the average particle size is 0.1 μm or more, the dispersibility in the positive electrode precursor is excellent. If the average particle size is 10 μm or less, the surface area of the alkali metal compound increases, so the decomposition reaction is carried out efficiently. In addition, the average particle size of the alkali metal compound in the positive electrode precursor is preferably smaller than the average particle size of the activated carbon described above. If the average particle size of the alkali metal compound is smaller than the average particle size of the activated carbon, the electron conduction of the positive electrode active material layer is improved, so it can contribute to the low resistance of the electrode body or the storage element. There is no particular limitation on the method for determining the average particle size of the alkali metal compound in the positive electrode precursor, and it can be calculated based on the SEM image and SEM-EDX image of the cross section of the positive electrode active material layer. Regarding the method for forming the cross section of the positive electrode active material layer, BIB processing can be used to irradiate an Ar beam from the top of the positive electrode and make a smooth cross section along the end of a shielding plate disposed directly above the sample. The alkali metal compound can be finely divided by various methods, for example, a pulverizer such as a ball mill, a bead mill, a ring mill, a jet mill, or a rod mill can be used.
[0101] Regarding the content of the alkali metal compound contained in the positive electrode active material layer of the positive electrode precursor, when the total mass of the positive electrode active material is set to 100 mass%, it is preferably 15.0 mass% or more and 45.0 mass% or less. If the value is 15.0 mass% or more, a sufficient amount of alkali metal ions can be pre-doped in the negative electrode, and the capacity of the non-aqueous alkali metal storage element is improved. If the value is 45.0 mass% or less, the electron conduction in the positive electrode precursor can be improved, so the alkali metal compound can be efficiently decomposed. Regarding the positive electrode precursor, in addition to the alkali metal compound, in the case of containing more than two alkali metal compounds or alkaline earth metal compounds, it is preferred that the total amount of the alkali metal compound and the alkaline earth metal compound is within the above range. The residual amount of the alkali metal compound in the positive electrode, that is, the alkali metal compound after the alkali metal doping process, is preferably 15 mass% or less relative to the amount of the alkali metal compound contained in the positive electrode precursor. If the amount of the alkali metal compound in the positive electrode is less than 15% by mass relative to the amount of the alkali metal compound in the positive electrode precursor, it means that more than 85% by mass of the alkali metal compound is decomposed in the alkali metal doping step and is fully pre-doped. The quantification of the above-mentioned alkali metal elements and alkaline earth metal elements in the positive electrode and the positive electrode precursor can be performed by ICP-AES, atomic absorption spectrometry, fluorescent X-ray analysis, neutron radiation analysis, ICP-MS, etc.
[0102] [Other components of positive electrode active material layer]
[0103] The positive electrode active material layer of the positive electrode and the positive electrode precursor in the present disclosure may contain, in addition to the positive electrode active material and the alkali metal compound, optional components such as a dispersant, a conductive filler, a binder, and a pH adjuster as necessary.
[0104] (Dispersant)
[0105] There is no particular limitation on the dispersant, and for example, one or more selected from carboxymethyl cellulose, polycarboxylic acid, polycarboxylate, polyvinyl pyrrolidone, polyvinyl alcohol, surfactant, etc. are suitable. The dispersant particularly preferably comprises carboxymethyl cellulose, and one or more selected from polyvinyl pyrrolidone and polyvinyl alcohol. Regarding the content of the dispersion stabilizer in the positive electrode active material layer of the positive electrode precursor, it is preferably 1.0 parts by mass or more and 7.0 parts by mass or less relative to 100 parts by mass of the solid content in the positive electrode active material layer. If the amount of the dispersion stabilizer is 7.0 parts by mass or less, the entry and exit and diffusion of ions in the positive electrode active material will not be hindered, showing high input-output characteristics.
[0106] (Conductive filler)
[0107] The conductive filler is preferably composed of a conductive carbonaceous material having a higher conductivity than the positive electrode active material. As such a conductive filler, for example, one or more selected from carbon black, graphite, graphene, etc. and mixtures thereof are preferred. Carbon black includes, for example, Ketjen black, acetylene black, etc. Graphite includes, for example, flaky graphite, etc. As the conductive filler, carbon black is particularly suitable.
[0108] Regarding the content of the conductive filler in the positive active material layer of the positive electrode precursor, relative to 100 parts by mass of the positive active material, it is preferably 0 parts by mass or more and 20 parts by mass or less, and more preferably 1 parts by mass or more and 15 parts by mass or less. From the aspect of high input, it is preferred to mix as many conductive fillers as possible. If the mixing amount is less than 20 parts by mass, the content ratio of the positive active material in the positive active material layer increases, so the energy density per unit volume of the positive active material layer is improved, and thus it is preferred.
[0109] (Binder)
[0110] As a binder, for example, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), fluororubber, polyimide, latex, styrene-butadiene copolymer, acrylic copolymer, etc. can be used. Regarding the content of the binder in the positive electrode active material layer, relative to 100 parts by mass of the positive electrode active material, it is preferably in the range of 0 parts by mass or more and 20 parts by mass or less, and more preferably in the range of 0.1 parts by mass or more and 15 parts by mass or less.
[0111] (pH adjuster)
[0112] When water is used as the solvent of the coating liquid for forming the positive electrode active material layer, the coating liquid may become alkaline by adding an alkali metal compound. Therefore, in the coating liquid for forming the positive electrode active material layer, a pH adjuster may be added to the coating liquid as needed. There is no particular limitation on the pH adjuster, for example, hydrogen halides such as hydrogen fluoride, hydrogen chloride, and hydrogen bromide; halogen oxygen-containing acids such as hypochlorous acid, chlorous acid, and chloric acid; carboxylic acids such as formic acid, acetic acid, citric acid, oxalic acid, lactic acid, maleic acid, and fumaric acid; sulfonic acids such as methanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid; acids such as nitric acid, sulfuric acid, phosphoric acid, boric acid, and carbon dioxide; and the like.
[0113] [Positive electrode collector]
[0114] The material constituting the positive electrode current collector is not particularly limited as long as it has high electron conductivity and does not dissolve into the electrolyte solution or deteriorate due to reaction with the electrolyte or ions, etc. Metal foil is preferred. Aluminum foil is more preferred as the positive electrode current collector in the nonaqueous alkali metal storage element of the present disclosure.
[0115] The metal foil may be a common metal foil without concavoconvex or through-holes, or may be a metal foil with concavoconvexity that has been subjected to embossing, chemical etching, electrolytic deposition, sandblasting, etc., or may be a metal foil with through-holes such as a metal sheet, a punched metal, or an etched foil. From the perspective of the pre-doping treatment described later, a non-porous aluminum foil is further preferred, and the surface of the aluminum foil is particularly preferably roughened. Regarding the thickness of the positive electrode collector, there is no particular restriction as long as the shape and strength of the positive electrode can be fully maintained, for example, preferably 1 μm or more and 100 μm or less.
[0116] An anchor layer containing a conductive material such as graphite, flaky graphite, carbon nanotubes, graphene, Ketjen black, acetylene black, vapor-grown carbon fiber, etc. is preferably provided on the surface of the metal foil. By providing the anchor layer, the electrical conduction between the positive electrode collector and the positive electrode active material layer can be improved, and low resistance can be achieved. The thickness of the anchor layer is preferably 0.1 μm or more and 5 μm or less on each single side of the positive electrode collector.
[0117] The thickness of the positive electrode active material layer of the positive electrode precursor disclosed in the present invention is preferably 10 μm to 200 μm on each single side of the positive electrode collector. The thickness of the positive electrode active material layer is more preferably 20 μm to 100 μm on each single side, and further preferably 30 μm to 80 μm. If the thickness is 10 μm or more, sufficient charge and discharge capacity can be exhibited. On the other hand, if the thickness is 200 μm or less, the ion diffusion resistance in the electrode can be maintained at a low level. Therefore, sufficient output characteristics can be obtained, and the volume of the battery cell can be reduced, thereby improving the energy density. It should be noted that, in the case where the positive electrode collector has through holes or bumps, the thickness of the positive electrode active material layer refers to the average value of the thickness of each single side of the portion of the positive electrode collector that does not have through holes or bumps.
[0118] <Negative electrode>
[0119] The negative electrode in the nonaqueous alkali metal energy storage device of the present disclosure typically includes a negative electrode current collector layer and a negative electrode active material layer formed on one or both surfaces of the negative electrode current collector.
[0120] [Negative Electrode Active Material Layer]
[0121] The negative electrode active material layer preferably contains a negative electrode active material, and may further contain, in addition to the negative electrode active material, optional components such as a dispersant, a conductive filler, a binder, and a metal oxide as necessary.
[0122] Regarding the negative electrode in the present disclosure, the secondary electron image obtained by photographing the surface of the negative electrode active material layer at a magnification of 100 times using a scanning electron microscope without exposure to the atmosphere is binarized with the brightness of each pixel, and there are bright field areas and multiple dark field areas in the image obtained by binarization (hereinafter also referred to as "binarized image"), and the multiple dark field areas correspond to the deposits formed on the surface of the above-mentioned negative electrode active material layer. The dark field area is discrete compared to the bright field area, and preferably there are multiple independent dark field areas surrounded by the bright field area. The total area of the dark field area is preferably smaller than the total area of the bright field area. In contrast, it is preferred that the bright field area is continuous compared to the dark field area. However, the bright field area does not need to be a single area, and there may be multiple independent bright field areas surrounded by the dark field area.
[0123] Regarding the negative electrode in the present disclosure, in the above-mentioned binary image, when 1 pixel is set to 1.46 μm, the maximum value of the area occupied by each dark field region (hereinafter also referred to as “the maximum area of the dark field region”) S[pixel 2] is 4000 or less, preferably 4000 or less and 500 or more. In other words, the maximum area S of the dark field area refers to the area of the largest dark field area among the multiple dark field areas that exist. The upper limit of the maximum area S of the dark field area is 4000 or less, preferably 3500 or less, and more preferably 3000 or less. The lower limit of the maximum area S of the dark field area, which can be arbitrarily combined with these upper limits, is not particularly limited, and can be 500 or more, 1000 or more, 1500 or more, 2000 or more, 2400 or more, or 2408 or more. The maximum area S of the dark field area is particularly preferably 2408 or more and 3000 or less.
[0124] In the non-aqueous alkali metal storage element disclosed in the present invention, by making the maximum area S of the dark field region of the negative electrode less than 4000, a non-aqueous lithium storage element with high high-temperature cycle durability can be provided. As a reason for this, although not limited to theory, the inventors have conducted research as follows. That is, in the alkali metal doping process, a SEI (Solid Electrolyte Interphase) coating is formed on the surface of the negative electrode, typically by decomposing the electrolyte. At this time, in the existing non-aqueous lithium storage element, relatively large bumps and depressions are formed on the surface of the SEI coating. It can be seen that deposits derived from alkali metals are easily accumulated on the convex parts of the SEI coating, and the deposits become obstacles to the insertion of lithium ions into the negative electrode active material layer during charge and discharge cycles, especially during high-temperature cycles. In addition, in the concave parts of the SEI coating, during charge and discharge cycles, due to the concentration of current, especially during high-temperature cycles, lithium ions may be deactivated. In contrast, in the non-aqueous alkali metal storage element disclosed in the present invention, the maximum area S [pixel] of the dark field region is less than 4000. 2 ] is adjusted to less than 4000. By reducing the value of the maximum area of the dark field region, the distribution of the deposits formed on the surface of the negative electrode is more uniform, and as a result, the entry and exit of lithium ions into the negative electrode active material layer becomes efficient during high-temperature cycling. Therefore, according to the non-aqueous alkali metal storage element disclosed in the present invention, a non-aqueous lithium storage element with high high-temperature cycle durability can be provided.
[0125] The dark field region corresponds to deposits deposited on the surface of the negative electrode active material layer. The deposits are believed to be derived from side reaction products generated in the alkali metal doping step, and although not limited thereto, preferably contain compounds derived from alkali metals, more preferably contain compounds derived from metallic lithium (Li).
[0126] In the above binary image, when 1 pixel is set to 1.46 μm, if the average value of the area occupied by each dark field region (hereinafter also referred to as the “average area of the dark field region”) is set to T[pixel 2], the upper limit of T is preferably 800 or less, more preferably 700 or less, further preferably 600 or less, further preferably 500 or less, and particularly preferably 400 or less. The lower limit of the average area T of the dark field region, which can be arbitrarily combined with these upper limits, is not particularly limited, and can preferably be 50 or more, 100 or more, 150 or more, or 200 or more. Although not limited to this theory, in the disclosed non-aqueous alkali metal storage element, by making the average area T of the dark field region of the negative electrode within the above range, the distribution of the deposits formed on the surface of the negative electrode is more uniform, and as a result, a non-aqueous lithium storage element with higher high temperature cycle durability can be provided.
[0127] (Negative electrode active material)
[0128] The negative electrode active material may be a material that can absorb and release alkali metal ions, and specifically, carbon materials, titanium oxides, silicon, silicon oxides, silicon alloys, silicon compounds, tin, and tin compounds can be exemplified.
[0129] The negative electrode active material of this embodiment preferably includes a carbon material. Examples of the carbon material include a non-graphitizable carbon material; an easily graphitizable carbon material; carbon black; carbon nanoparticles; activated carbon; artificial graphite; natural graphite; graphitized mesophase carbon microspheres; graphite whiskers; amorphous carbon materials such as polyacene-based materials; carbon materials obtained by heat-treating carbon precursors such as petroleum-based pitch, coal-based pitch, mesophase carbon microspheres, coke, and synthetic resins (such as phenolic resins); thermal decomposition products of furfuryl alcohol resins or novolac resins; fullerenes; carbon nanofibers; and composite carbon materials thereof.
[0130] Among these, from the aspect of reducing the resistance of the negative electrode, it is preferred that (1) one or more of the graphite materials selected from artificial graphite, natural graphite, graphitized mesophase carbon microspheres, graphite whiskers, high specific surface area graphite, etc. and (2) one or more of the carbonaceous material precursors such as petroleum-based pitch, coal-based pitch, mesophase carbon microspheres, coke, synthetic resins (such as phenolic resins, etc.) are heat-treated to make the graphite material and the composite carbon material derived from the carbonaceous material precursor composite. As a carbonaceous material precursor, as long as it is heat-treated to become a carbonaceous material, there is no particular restriction, and petroleum-based pitch or coal-based pitch are particularly preferred.
[0131] The BET specific surface area of the composite carbon material is preferably 1 m 2 / g above 50m 2 / g or less, more preferably 1.5m 2 / g above 40m 2 / g or less, more preferably 2m 2 / g above 25m 2 / g or less. If the BET specific surface area of the composite carbon material is 1m 2 / g or more, it is possible to ensure that there are enough reaction sites with lithium ions in the non-aqueous electrolyte, so that high input-output characteristics can be exhibited. 2 / g or less, the charge and discharge efficiency of lithium ions is improved, and the reductive decomposition of the non-aqueous electrolyte during charge and discharge is suppressed, so that high high-load charge and discharge cycle characteristics can be exhibited.
[0132] The average pore size of the composite carbon material is preferably 1.5 nm to 25 nm, more preferably 2 nm to 22 nm, further preferably 3 nm to 20 nm, and particularly preferably 3.5 nm to 18 nm. If the average pore size of the composite carbon material is 1.5 nm or more, there are more pores larger than the size of the solvated lithium ions in the non-aqueous electrolyte (about 0.9 nm to 1.2 nm), so the diffusion of the solvated lithium ions in the composite carbon material becomes good, and the non-aqueous lithium storage element using it can show high input-output characteristics. On the other hand, if the average pore size of the composite carbon material is 25 nm or less, the packing density of the negative electrode active material layer using it can be fully improved, so that a high energy density can be shown.
[0133] The composite carbon material may be granular, and its average particle size is preferably 1 μm or more and 10 μm or less, more preferably 2 μm or more and 8 μm or less, and further preferably 3 μm or more and 6 μm or less. If the average particle size of the composite carbon material is 1 μm or more, the charge and discharge efficiency of lithium ions can be improved, and thus high high-load charge and discharge cycle characteristics can be exhibited. If the average particle size of the composite carbon material is 10 μm or less, the reaction sites with lithium ions in the non-aqueous electrolyte are increased, and thus high input-output characteristics can be exhibited.
[0134] The mass ratio of the carbonaceous material in the composite carbon material relative to the graphite material is preferably 1% by mass or more and 20% by mass or less, more preferably 1.2% by mass or more and 15% by mass or less, further preferably 1.5% by mass or more and 10% by mass or less, and further preferably 2% by mass or more and 5% by mass or less. If the mass ratio of the carbonaceous material is more than 1% by mass, the reaction sites with the lithium ions in the non-aqueous electrolyte can be fully increased by the carbonaceous material, and the desolvation of the lithium ions also becomes easy, so it is possible to show high input-output characteristics. If the mass ratio of the carbonaceous material is less than 20% by mass, the solid diffusion of the lithium ions between the carbonaceous material and the graphite material can be well maintained, so it is possible to show high input-output characteristics. In addition, since the charge and discharge efficiency of lithium ions can be improved, it is possible to show high high-load charge and discharge cycle characteristics.
[0135] The composite carbon material is preferably doped with alkali metal ions. In this case, the doping amount of alkali metal ions per unit mass of the composite carbon material (mAh / g) is preferably 50mAh / g to 700mAh / g, more preferably 70mAh / g to 650mAh / g, further preferably 90mAh / g to 600mAh / g, and further preferably 100mAh / g to 550mAh / g. The greater the Li doping amount, the longer the life of the non-aqueous lithium storage element can be extended. Therefore, the doping amount of alkali metal ions (%) is preferably 80% to 100%, more preferably 85% to 100%.
[0136] (Other components of negative electrode active material layer)
[0137] In addition to the negative electrode active material, the negative electrode active material layer may further contain optional components such as a dispersant, a conductive filler, and a binder as required. The dispersant, conductive filler, and binder in the positive electrode active material layer may be appropriately selected from the materials exemplified above as the dispersant, conductive filler, and binder in the negative electrode active material layer for use.
[0138] The content ratio of the dispersant and the binder in the positive electrode active material layer can be within the above range as the content ratio of the dispersant and the binder in the negative electrode active material, respectively. The mixing amount of the conductive filler in the negative electrode active material layer is preferably 25 parts by mass or less, and more preferably 5% by mass or more and 20% by mass or less relative to 100 parts by mass of the negative electrode active material.
[0139] (Thickness of negative electrode active material layer)
[0140] The thickness of the negative electrode active material layer is preferably 10 μm to 70 μm on each single side, more preferably 20 μm to 60 μm. If the thickness is 10 μm or more, a good charge and discharge capacity can be exhibited. On the other hand, if the thickness is 70 μm or less, the volume of the battery cell can be reduced, thereby increasing the energy density. In the case where the negative electrode collector has holes, the thickness of the negative electrode active material layer refers to the average value of the thickness of each single side of the portion of the negative electrode collector that does not have holes.
[0141] [Negative electrode current collector]
[0142] As the material constituting the negative electrode collector of the present invention, it is preferred that the material has high electronic conductivity, does not dissolve in the electrolyte, does not deteriorate due to reaction with the electrolyte or ions, etc., and it can be a metal foil, for example. There is no particular limitation on such a metal foil, and examples thereof include aluminum foil, copper foil, nickel foil, stainless steel foil, etc. As the negative electrode collector in the non-aqueous alkali metal storage element of the present invention, copper foil is preferred. The metal foil used as the negative electrode collector can be a common metal foil without concave-convex or through-holes, or a metal foil with concave-convex that has been subjected to embossing, chemical etching, electrolytic deposition, sandblasting, etc., or a metal foil with through-holes such as a metal plate mesh, a punched metal, and an etched foil. Regarding the thickness of the negative electrode collector, there is no particular limitation as long as the shape and strength of the negative electrode can be fully maintained, and it is, for example, not less than 1 μm and not more than 100 μm.
[0143] <Partition>
[0144] The positive electrode precursor and the negative electrode are stacked across the separator, or stacked and wound to form an electrode laminate or electrode winding body having a positive electrode precursor, a negative electrode and a separator. As a separator, a polyethylene microporous film or a polypropylene microporous film used for a lithium ion secondary battery or a cellulose nonwoven paper used in a double electric layer capacitor can be used. A film composed of organic or inorganic particles can be stacked on one side or both sides of these separators. In addition, organic or inorganic particles can be included inside the separator.
[0145] The thickness of the separator is preferably 5 μm or more and 35 μm or less. By making the thickness of 5 μm or more, self-discharge due to internal micro short circuit tends to be reduced, which is preferred. On the other hand, by making the thickness of 35 μm or less, the output characteristics of the storage element tend to increase, which is preferred.
[0146] The thickness of the film composed of organic or inorganic particles is preferably 1 μm or more and 10 μm or less. By making it 1 μm or more, self-discharge due to internal micro short circuit tends to be reduced, which is preferred. On the other hand, by making it 10 μm or less, the output characteristics of the storage element tend to increase, which is preferred.
[0147] <Exterior body>
[0148] As the outer body, a metal can, a laminated film, etc. can be used. As the metal can, an aluminum metal can is preferred. The metal can can be, for example, in a square, round, cylindrical, etc. shape. As the laminated film, a film formed by laminating a metal foil and a resin film is preferred, and a film having a three-layer structure consisting of an outer resin film / metal foil / inner resin film can be exemplified. The outer resin film is used to prevent the metal foil from being damaged due to contact, etc., and resins such as nylon or polyester can be appropriately used. The metal foil is used to prevent the penetration of moisture and gas, and foils of copper, aluminum, stainless steel, etc. can be appropriately used. In addition, the inner resin film is used to protect the metal foil from being damaged by the electrolyte contained inside, and is also used to perform melt sealing when the outer body is heat-sealed, and polyolefins, acid-modified polyolefins, etc. can be appropriately used.
[0149] <Electrolyte>
[0150] The electrolyte in the present disclosure is a non-aqueous electrolyte. That is, the electrolyte contains a non-aqueous solvent. The non-aqueous electrolyte contains an electrolyte salt containing alkali metal ions (such as lithium ions). Taking the total amount of the non-aqueous electrolyte as a reference, the electrolyte salt is preferably 0.5 mol / L or more. That is, the non-aqueous electrolyte contains an alkali metal salt as an electrolyte. As the non-aqueous solvent contained in the non-aqueous electrolyte, for example, cyclic carbonates represented by ethylene carbonate, propylene carbonate, etc., and chain carbonates represented by dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, etc. can be cited.
[0151] In the non-aqueous electrolyte, it is preferred that in addition to the electrolyte salt, a cyclic compound selected from cyclic carbonates and cyclic sulfates is further contained, and it is more preferred that a cyclic carbonate and a cyclic sulfate are contained. Cyclic carbonates can be contained in the non-aqueous electrolyte as a non-aqueous solvent. Cyclic sulfates can be contained in the non-aqueous electrolyte as an additive, and can have the function of forming a high-quality coating by being decomposed on the surface of the negative electrode. When the non-aqueous electrolyte contains a cyclic compound selected from cyclic carbonates and cyclic sulfates, a SEI coating of high-quality composition can be formed on the surface of the negative electrode, and a coating with high protective function that can inhibit side reactions occurring on the surface of the negative electrode can be easily formed. As a result, the durability of the completed non-aqueous lithium storage element is improved. As cyclic carbonates, alkylene carbonates, such as ethylene carbonate and propylene carbonate, etc. can be cited. As cyclic sulfates, alkylene sulfates, such as vinyl sulfate (1,3,2-dioxathiolane-2,2-dioxide), etc. can be cited.
[0152] As the electrolyte salt containing alkali metal ions dissolved in the non-aqueous solvent as mentioned above, for example, MFSI, MBF4, MPF6, MClO4, LiB(C2O4)2, LiBF2(C2O4), etc., in which M is Li, Na, K, Rb or Cs, can be used. The non-aqueous electrolyte in the present disclosure may contain at least one or more alkali metal ions, may contain more than two alkali metal salts, or may contain alkali metal salts and alkaline earth metal salts selected from beryllium salts, magnesium salts, calcium salts, strontium salts, and barium salts. In the case where the non-aqueous electrolyte contains more than two alkali metal salts, by allowing cations with different Stokes radii to exist in the non-aqueous electrolyte, the viscosity increase at low temperature can be suppressed, thereby improving the low temperature characteristics of the non-aqueous alkali metal storage element. In the case where the non-aqueous electrolyte contains alkaline earth metal ions other than the above-mentioned alkali metal ions, the capacity of the non-aqueous alkali metal storage element can be increased.
[0153] There is no particular limitation on the method of containing two or more of the above-mentioned alkali metal salts in a non-aqueous electrolyte, or the method of containing an alkali metal salt and an alkaline earth metal salt in a non-aqueous electrolyte. For example, there can be cited a method of pre-dissolving an alkali metal salt containing two or more alkali metal ions in a non-aqueous electrolyte; a method of pre-dissolving an alkali metal salt and an alkaline earth metal salt in a non-aqueous electrolyte; a method of making the positive electrode precursor contain one or more of the following components and decomposing them in the pre-doping process described later, etc., wherein the components are: making M in the following formula be one or more carbonates such as M2CO3 selected from Na, K, Rb and Cs; oxides such as M2O; hydroxides such as MOH; halides such as MF and MCl; carboxylates such as RCOOM (wherein R is H, alkyl or aryl); and alkaline earth metal carbonates selected from BeCO3, MgCO3, CaCO3, SrCO3 or BaCO3, as well as alkaline earth metal oxides, alkaline earth metal hydroxides, alkaline earth metal halides and alkaline earth metal carboxylates.
[0154] The electrolyte salt concentration in the electrolyte is preferably in the range of 0.5 to 2.0 mol / L. At an electrolyte salt concentration of 0.5 mol / L or more, anions are sufficiently present to maintain the capacity of the non-aqueous alkali metal storage element. On the other hand, at an electrolyte salt concentration of 2.0 mol / L or less, the salt is sufficiently dissolved in the electrolyte to ensure the appropriate viscosity and conductivity of the electrolyte. In the case where the non-aqueous electrolyte contains two or more alkali metal salts, or contains an alkali metal salt and an alkaline earth metal salt, the total value of their salt concentrations is preferably 0.5 mol / L or more, more preferably in the range of 0.5 to 2.0 mol / L.
[0155] The water content contained in the non-aqueous electrolyte is preferably more than 0ppm and less than 500ppm. If the water content is more than 0ppm, the alkali metal compound in the positive electrode precursor can be slightly dissolved, so it can be pre-doped under mild conditions, thereby achieving high capacity and low resistance. If the water content is less than 500ppm, the decomposition of the electrolyte is suppressed, thereby improving the high temperature storage characteristics. The water content in the electrolyte can be measured by the above-mentioned Karl Fischer method.
[0156] "Method for producing non-aqueous alkali metal energy storage device"
[0157] <Manufacturing of positive electrode precursor>
[0158] In the present disclosure, the positive electrode precursor constituting the positive electrode of the non-aqueous alkali metal storage element can be manufactured by the manufacturing technology of the electrode in the known lithium ion battery, double electric layer capacitor, etc. For example, the positive electrode active material and the alkali metal compound and other optional components used as needed can be dispersed or dissolved in water or an organic solvent to prepare a slurry coating liquid, and the coating liquid is applied to one or both sides of the positive electrode collector to form a coating film, and the coating film is dried to obtain a positive electrode precursor. The obtained positive electrode precursor can also be further pressed to adjust the film thickness or bulk density of the positive electrode active material layer.
[0159] The preparation method of the coating liquid for forming the positive electrode active material layer is not particularly limited, and can be suitably carried out using a homogenizing disperser, a multi-axis disperser, a planetary mixer, a thin film gyratory high-speed mixer and other dispersers. In order to obtain a coating liquid with a good dispersion state, it is preferred to disperse the coating liquid at a peripheral speed of more than 1m / s and less than 50m / s. If the peripheral speed is more than 1m / s, various materials can be well dissolved or dispersed, and thus preferably. If the peripheral speed is less than 50m / s, various materials will not be destroyed by the heat or shear force generated by the dispersion, and re-agglomeration can be suppressed, and thus preferably.
[0160] Regarding the dispersion degree of the coating liquid, the particle size measured by a particle size meter is preferably 0.1 μm or more and 100 μm or less. Regarding the upper limit of the dispersion degree, the particle size measured by a particle size meter is more preferably 80 μm or less, and further preferably 50 μm or less. If the particle size is within this range, the material will not be broken when preparing the coating liquid, and the nozzle clogging and the generation of coating film stripes during coating can be suppressed, and stable coating can be achieved.
[0161] The viscosity (ηb) of the coating liquid is preferably 1,000 mPa·s to 20,000 mPa·s, more preferably 1,500 mPa·s to 10,000 mPa·s, and further preferably 1,700 mPa·s to 5,000 mPa·s. If the viscosity (ηb) is 1,000 mPa·s or more, the dripping of the liquid during the formation of the coating film can be suppressed, and the width and thickness of the coating film can be well controlled. In addition, if the viscosity is 20,000 mPa·s or less, the pressure loss of the coating liquid in the flow channel is small when using a coating machine, and the coating can be stably applied, and the control of the coating film thickness becomes easy.
[0162] The TI value (thixotropic index value) of the coating liquid is preferably 1.1 or more, more preferably 1.2 or more, and further preferably 1.5 or more. When the TI value is 1.1 or more, the coating film width and thickness can be well controlled.
[0163] There is no particular restriction on the formation of the coating of the positive electrode active material layer, and a coating machine such as a die coater, a comma coater, a knife coater, or a gravure coater can be suitably used. The coating can be formed by a single layer coating, or it can be formed by multi-layer coating. In the case of multi-layer coating, the coating liquid composition can be adjusted in a manner such that the content of the components in each layer of the coating is different. When the coating is applied to the positive electrode collector, multiple strips of coating can be applied, intermittent coating can be applied, or multiple strips of intermittent coating can be applied.
[0164] When the positive electrode active material layer is formed on both sides of the positive electrode collector, the positive electrode collector can be coated and dried on one side, and then coated and dried on the other side successively, or the coating liquid can be simultaneously coated on both sides of the positive electrode collector and dried on both sides. In addition, in this case, the difference in thickness between the positive electrode active material layer on the surface and the back of the positive electrode collector is preferably less than 10% of the average thickness of the two. The closer the mass ratio and film thickness ratio of the positive electrode active material layer on the surface and the back are to 1.0, the less the charge and discharge load will be concentrated on one side, so the high-load charge and discharge cycle characteristics are improved.
[0165] After forming a coating of the positive electrode active material layer on the positive electrode current collector, the coating is dried. The coating of the positive electrode precursor is preferably dried using an appropriate drying method such as hot air drying, infrared (IR) drying, and preferably using far infrared, near infrared or hot air. Regarding the drying of the coating, it can be dried at a single temperature or by changing the temperature in multiple stages. It is also possible to combine a variety of drying methods for drying.
[0166] The drying temperature is preferably 25°C to 200°C, more preferably 40°C to 180°C, and further preferably 50°C to 160°C. If the drying temperature is 25°C or higher, the solvent in the coating film can be fully volatilized. On the other hand, if the drying temperature is 200°C or lower, cracking of the coating film due to rapid volatilization of the solvent or segregation of the binder due to migration can be suppressed, and oxidation of the positive electrode collector or the positive electrode active material layer can be suppressed.
[0167] When the total mass of the positive electrode active material layer is set to 100% by mass, the moisture contained in the dried positive electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less. If the water content is 0.1% by mass or more, the deterioration of the binder caused by excessive drying can be suppressed and low resistance can be achieved. If the water content is 10% by mass or less, the deactivation of alkali metal ions can be suppressed and high capacity can be achieved. In the case of using N-methyl-2-pyrrolidone (NMP) in the preparation of the coating solution, when the total mass of the positive electrode active material layer is set to 100%, the content of NMP in the dried positive electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less. The water content contained in the positive electrode active material layer can be measured by, for example, Karl Fischer titration (JIS 0068 (2001) "Method for Determination of Moisture in Chemical Products"). The amount of NMP contained in the positive electrode active material layer can be quantified as follows: the positive electrode active material layer is immersed in ethanol with a mass 50 to 100 times the mass of the positive electrode active material layer at 25° C. for 24 hours to extract NMP, and then GC / MS measurement is performed to quantify it based on a pre-made calibration curve.
[0168] The pressing of the positive electrode active material layer can be appropriately performed using a suitable press such as an oil press, a vacuum press, and a roller press. The film thickness, bulk density, and electrode strength of the positive electrode active material layer can be adjusted by the pressing pressure, the gap between the pressing rollers, and the surface temperature of the pressing portion described later. The pressing pressure is preferably 0.5 kN / cm or more and 20 kN / cm or less, more preferably 1 kN / cm or more and 10 kN / cm or less, and further preferably 2 kN / cm or more and 7 kN / cm or less. If the pressing pressure is 0.5 kN / cm or more, the electrode strength can be fully improved. On the other hand, if the pressing pressure is 20 kN / cm or less, the positive electrode active material layer can be adjusted to the desired film thickness or bulk density without bending and wrinkling of the positive electrode precursor. In the case of using a roller press in the pressing, the gap between the pressing rollers can be set to a suitable value in accordance with the manner in which the positive electrode active material layer reaches the desired thickness and bulk density. The pressing speed can be set to a suitable speed at which the positive electrode precursor does not bend or wrinkle.
[0169] The surface temperature of the pressed portion may be room temperature or may be heated as required. When heated, the lower limit of the surface temperature of the pressed portion is preferably a temperature above the melting point of the adhesive used - 60°C, more preferably a temperature above the melting point of the adhesive - 45°C, and further preferably a temperature above the melting point of the adhesive - 30°C. On the other hand, when heated, the upper limit of the surface temperature of the pressed portion is preferably a temperature below the melting point of the adhesive used + 50°C. More preferably, it is a temperature below the melting point of the adhesive + 30°C, and further preferably, it is a temperature below the melting point of the adhesive + 20°C.
[0170] For example, when polyvinylidene fluoride (melting point 150°C) is used as the binder, the press part is preferably heated to 90°C to 200°C, more preferably 105°C to 180°C, and further preferably 120°C to 170°C. In addition, when styrene-butadiene copolymer (melting point 100°C) is used as the binder, the press part is preferably heated to 40°C to 150°C, more preferably 55°C to 130°C, and further preferably 70°C to 120°C.
[0171] The melting point of the binder can be obtained from the endothermic peak position of DSC (Differential Scanning Calorimetry). For example, using a differential scanning calorimeter "DSC7" manufactured by Perkin Elmer, 10 mg of the sample resin is placed in a measuring cell and the temperature is raised from 30°C to 250°C at a heating rate of 10°C / min in a nitrogen atmosphere. The endothermic peak temperature during the heating process is the melting point.
[0172] Multiple pressings can be performed while changing the pressing pressure, gap, speed, and surface temperature of the pressing portion. When the positive electrode active material layer is coated with multiple strips, it is preferably cut longitudinally before pressing. When the positive electrode precursor is pressed without longitudinally cutting the positive electrode active material layer coated with multiple strips, excessive stress will be applied to the positive electrode collector portion that is not coated with the positive electrode active material layer, which may cause wrinkles. The positive electrode active material layer can be longitudinally cut again after pressing.
[0173] In the non-aqueous alkali metal storage element disclosed in the present invention, it is planned to pre-dope the negative electrode with alkali metal ions. As the pre-doping method, the following method is preferably used: assemble the storage element using a positive electrode precursor, a negative electrode, a separator, an outer casing and a non-aqueous electrolyte containing an alkali metal compound, and then apply a voltage between the positive electrode precursor and the negative electrode. By applying the voltage, the alkali metal compound in the positive electrode precursor decomposes to release cations, and the cations are reduced at the negative electrode, thereby pre-doping the negative electrode. The positive electrode precursor disclosed in the present invention becomes a positive electrode by undergoing such an alkali metal doping process of the negative electrode. In the positive electrode active material layer of the positive electrode that has undergone the alkali metal doping process of the negative electrode, pores are formed by the decomposition of the alkali compound, and the effective area of the positive electrode active material layer is increased.
[0174] Since the alkali metal compound in the positive electrode active material layer of the positive electrode precursor is used as a doping source for the negative electrode in the alkali metal doping process, the content of the alkali metal compound in the positive electrode active material layer of the positive electrode that has undergone the alkali metal doping process is reduced compared to the content of the alkali metal compound in the positive electrode active material layer of the positive electrode precursor. The mass ratio C (mass %) of the alkali metal compound relative to the total mass of the positive electrode active material layer of the positive electrode is 0.1≤C≤7.0, preferably 0.5≤C≤6.0, more preferably 1.0≤C≤5.0, and further preferably 1.5≤C≤4.5.
[0175] <Manufacturing of negative electrode>
[0176] The negative electrode can be manufactured by forming a negative electrode active material layer on one side or both sides of the negative electrode collector. In a representative manner, the negative electrode active material layer is fixed to the negative electrode collector. The negative electrode can be manufactured by known manufacturing techniques for electrodes in lithium ion batteries, double-layer capacitors, etc. For example, various materials containing negative electrode active materials can be dispersed or dissolved in water or an organic solvent to prepare a slurry-like coating liquid, and the coating liquid is applied to one side or both sides of the negative electrode collector to form a coating film, which is dried to obtain the negative electrode. The obtained negative electrode can also be further pressed to adjust the film thickness or bulk density of the negative electrode active material layer. The preparation of the coating liquid for forming the negative electrode active material layer, the application of the coating liquid on the negative electrode collector, the drying and pressing of the coating film can be carried out according to the above-mentioned methods in the manufacture of the positive electrode precursor.
[0177] <Assembly process electrode assembly production>
[0178] In the assembly process, for example, the positive electrode precursor and the negative electrode cut into a single piece shape can be stacked with a separator, and the positive terminal and the negative terminal can be connected to the obtained stack to produce an electrode stack. Alternatively, the positive electrode precursor and the negative electrode can be stacked and wound with a separator, and the positive terminal and the negative terminal can be connected to the obtained wound body to produce an electrode wound body. The shape of the electrode wound body can be cylindrical or flat.
[0179] There is no particular limitation on the method for connecting the positive terminal and the negative terminal, and methods such as resistance welding and ultrasonic welding can be used. Preferably, the electrode body (electrode laminate or electrode winding) connected to the terminal is dried to remove the residual solvent. The drying method is not limited, and it can be dried by vacuum drying or the like. The residual solvent is preferably 1.5% by mass or less relative to the total mass of the positive electrode active material layer or the negative electrode active material layer. If the residual solvent is more than 1.5% by mass, there is solvent residue in the system, which deteriorates the self-discharge characteristics, and is therefore not preferred.
[0180] The dried electrode body is preferably stored in an outer body represented by a metal can or a laminated film in a dry environment with a dew point below -40°C, leaving only one opening for injecting a non-aqueous electrolyte for sealing. If the dew point is higher than -40°C, moisture will adhere to the electrode body, and water will remain in the system, deteriorating the self-discharge characteristics, which is not preferred. The sealing method of the outer body is not particularly limited, and methods such as heat sealing and pulse sealing can be used.
[0181] <Injection, impregnation, and sealing process>
[0182] After the assembly process, a non-aqueous electrolyte is injected into the electrode body housed in the outer body. After the injection, it is preferred to further perform infiltration, and fully impregnate the positive electrode precursor, the negative electrode and the separator with the non-aqueous electrolyte. In a state where at least a portion of the positive electrode precursor, the negative electrode and the separator are not impregnated with the electrolyte, the alkali metal doping is uneven in the alkali metal doping process described later, so the resistance of the obtained non-aqueous alkali metal storage element increases or the durability decreases. There is no particular limitation on the method of infiltration, for example, the following method can be used: the electrode body after the injection is placed in a reduced pressure chamber in a state where the outer body is open, a vacuum pump is used to make the chamber a reduced pressure state, and then the pressure is restored to the atmospheric pressure; etc. After the infiltration, the electrode body in the state where the outer body is open can be sealed under reduced pressure, thereby being sealed.
[0183] <Alkali Metal Doping Step>
[0184] In the alkali metal doping step, a voltage is preferably applied between the positive electrode precursor and the negative electrode to decompose an alkali metal compound preferably contained in the positive electrode precursor to release alkali metal ions, and the alkali metal ions are reduced at the negative electrode, thereby pre-doping the negative electrode active material layer with alkali metal ions.
[0185] In the alkali metal doping step, the alkali metal compound may be included in the positive electrode precursor in any manner. For example, the alkali metal compound may be present between the positive electrode collector and the positive electrode active material layer, or may be present on the surface of the positive electrode active material layer. The alkali metal compound is preferably included in the positive electrode active material layer formed on the positive electrode collector of the positive electrode precursor.
[0186] In the alkali metal doping process, as the alkali metal compound in the positive electrode precursor is oxidatively decomposed, gases such as CO2 are generated. Therefore, when a voltage is applied, it is preferred to adopt a means to release the generated gas to the outside of the outer body. As such means, for example, there can be cited: a method of applying voltage in a state where a portion of the outer body is opened; a method of pre-setting a suitable gas release means such as an exhaust valve, a gas permeable membrane, etc. on a portion of the outer body, and applying voltage in this state; and the like.
[0187] In order to maximize the dark field area S[pixel 2 ] and the average area T[pixel 2 ] Adjust the scope of this disclosure and the preferred scope, preferably in the alkali metal doping process, the SEI film is formed more uniformly (to make the bumps smaller) on the negative electrode surface of the negative electrode. In the existing alkali metal doping process, a certain current rate (a certain current value) that causes oxidative decomposition of the alkali metal compound is typically used for doping until the target voltage is reached. In contrast, the inventors have discovered that in the alkali metal doping process, before charging with a high current rate sufficient to cause oxidative decomposition of the alkali metal compound, a stage of forming the SEI film at a lower current rate is experienced, thereby being able to form the SEI film more uniformly (to make the bumps smaller) on the negative electrode surface of the negative electrode.
[0188] In more detail, the current rate (also called "C rate") in the film formation stage (first doping process) in the alkali metal doping process is preferably 0.05C or more and 0.20C or less. Here, the C rate is the relative ratio of the current during charging (discharging) to the charging capacity (discharging capacity), and the current value that fully charges (or discharges) a certain charging capacity (discharging capacity) in 1 hour is defined as 1C. The C rate in the present disclosure is calculated by the method described in the "C rate calculation method" described later. 1C corresponds to 4.0A. If the current value is preferably above 0.05C, the time required for the process is shortened, thereby increasing production efficiency. If the current value is preferably below 0.20C, there is a tendency to form an SEI film of uniform thickness, so it is easy to make the maximum area S [pixel] of the dark field area of the negative electrode 2] The disclosed range and the preferred range of the adjustment cost. As a result, the high temperature durability of the completed non-aqueous lithium storage element is improved. Regarding the film formation stage, although there is no limitation, for example, it is preferred to charge until the voltage reaches any voltage between 4.1V and 4.3V, and it is more preferred to perform constant current charging.
[0189] The C rate of the current value in the stage where the alkali metal compound undergoes oxidative decomposition (the second doping process) is preferably not less than 0.25C and not more than 1.0C. If the current value is not less than 0.25C, sufficient charge can be supplied during the oxidative decomposition of the alkali metal compound, and pre-doping can be efficiently implemented. If the current value is not more than 1.0C, the heat release of the battery cell can be suppressed, so the side reaction can be suppressed, and pre-doping can be efficiently implemented. Regarding the oxidative decomposition stage, although there is no limitation, for example, it is preferred to charge until the voltage reaches any voltage of not less than 4.4V and not more than 4.6V, and it is more preferred to perform constant current charging, and it is further preferred to perform constant current charging and then constant voltage charging. Regarding constant voltage charging, although there is no limitation, for example, it is preferably continued for not less than 1 hour and not more than 5 hours.
[0190] <Cyclic Aging Process>
[0191] Preferably, cyclic aging is performed after the alkali metal doping step. In the cyclic aging step, discharge to make the voltage between the positive electrode and the negative electrode reach a predetermined lower limit voltage and charge to reach a predetermined upper limit voltage are repeated for a predetermined number of times. By performing cyclic aging, the SEI film formed in the alkali metal doping step can be fixed.
[0192] <Aging process>
[0193] After the alkali metal doping step, the electrode body is preferably aged. By performing the aging, the formed SEI film can be stabilized. There is no particular limitation on the aging method, and for example, there is a method of keeping the electrode body in a high temperature environment for a predetermined time.
[0194] <Exhaust Process>
[0195] After the aging process, it is preferred to further exhaust gas to reliably remove the gas remaining in the electrolyte, the positive electrode and the negative electrode. In a state where gas remains in at least a portion of the electrolyte, the positive electrode and the negative electrode, ion conduction is hindered, so the resistance of the resulting non-aqueous alkali metal storage element will increase. There is no particular limitation on the exhaust method, for example, the following method can be used: the electrode body is placed in a decompression chamber with the outer body open, and a vacuum pump is used to make the chamber a decompression state; etc. After exhaust, the outer body can be sealed by sealing the outer body to produce a non-aqueous alkali metal storage element.
[0196] 《Applications of non-aqueous lithium storage devices》
[0197] By connecting a plurality of non-aqueous lithium storage elements of the present disclosure in series or in parallel, a storage module can be fabricated. In addition, the non-aqueous lithium storage elements and the storage module of the present disclosure can achieve both high input / output characteristics and safety at high temperatures. Therefore, they can be used in power regeneration assist systems, power load balancing systems, uninterruptible power supply systems, non-contact power supply systems, energy harvesting systems, energy storage systems, solar power generation energy storage systems, electric power steering systems, emergency power supply systems, in-wheel motor systems, idle stop systems, quick charging systems, smart grid systems, etc.
[0198] In addition, the non-aqueous lithium storage elements of the present disclosure can achieve both high input / output characteristics and safety at high temperatures, and thus can be mounted in vehicles such as electric vehicles, plug-in hybrid vehicles, hybrid vehicles, and electric two-wheel vehicles. The power regeneration assist system, electric power steering system, emergency power supply system, in-wheel motor system, idle stop system, or a combination thereof described above is suitable for mounting in vehicles.
[0199] Examples
[0200] Hereinafter, examples and comparative examples of the non-aqueous lithium storage elements of the present disclosure will be specifically described. However, the non-aqueous lithium storage elements of the present disclosure are not limited by any of the following examples and comparative examples.
[0201] 《Measurement and Evaluation Methods》
[0202] <Calculation Method of C Rate>
[0203] In the present disclosure, the C rate is a value obtained by the following method. That is, the laminated negative electrode single-pole battery unit before initial charging is placed in a thermostat set at a temperature of 25°C, and a constant current charging is performed at a current value of 0.16 mA / cm per unit electrode area of the negative electrode 2 to a voltage of 10 mV and a constant voltage charging is performed at a voltage of 10 mV, and the total charging capacity at this time is set as Q0 [Ah / g]. At this time, the constant voltage charging at a voltage of 10 mV is continued until the current value during the continuation of the constant voltage charging becomes less than 1.0 mA. In addition, when the total weight of the negative electrode active material and the carbon black conductive additive contained in the negative electrode is set as G [g], Q0 × G corresponds to 1C of this non-aqueous lithium storage element.
[0204] <Method for Obtaining SEM Image and Binarization Method>
[0205] In the present disclosure, the method for obtaining the SEM image of the surface of the negative electrode active material layer and the method for binarizing the SEM image are as follows. That is, after the non-aqueous lithium storage element is adjusted to a voltage of 4.0V, the outer body is removed in an argon box, and the negative electrode is taken out from the electrode laminate. The taken out negative electrode is cut into a size of 1 cm square, washed and air-dried with a carbonate solvent, and an SEM image of the surface of the negative electrode active material layer is obtained without exposure to the atmosphere. The detailed measurement conditions of the SEM image are as follows.
[0206] ·Measurement device: Field emission scanning electron microscope SU8220 manufactured by Hitachi High-Technologies Corporation
[0207] Accelerating voltage: 1kV
[0208] ·Measurement magnification: 100 times
[0209] Detector: Secondary electron detector
[0210] The portion corresponding to the scale bar was removed from the SEM image obtained above at a magnification of 100 times by trimming. The image thus obtained was filtered by a Gaussian filter with a filter size of (7×7) and binarized by Otsu's binarization method. Next, a closed process with a kernel size of (2×2) was performed with three iterations to obtain a binarized SEM image.
[0211] <Calculation of the Maximum Area S and Average Area T of the Dark Field Region>
[0212] The entire outline of the low brightness portion (dark field area) is detected from the binarized SEM image, and the area occupied by each pixel constituting the dark field area is calculated. Then, the maximum area S [pixel 2 ] and the average area T[pixel 2 ]. Among the pixels occupying the dark field area, the area is less than 100 pixels. 2 area and 300,000 pixels 2 The above areas are noise and are excluded from the calculation of the maximum area value and the average area value.
[0213] <High temperature cycle test>
[0214] The nonaqueous lithium storage element was placed in a thermostatic chamber and subjected to a charge-discharge cycle test for 1000 hours at a voltage range of 3.95 V to 2.80 V. During the cycle test, the temperature of the nonaqueous lithium storage element was adjusted in the thermostatic chamber to 65°C.
[0215] <Production of button-type negative electrode monopolar battery cell>
[0216] In an argon box, the negative electrode as the object is cut into a circle with a diameter of 16 mm. At this time, when the negative electrode used is a double-sided coated product, the composite material layer on one side is peeled off using a carbonate solvent, a wiping cloth, etc., and then cut. After that, a circular piece of metallic Li with a diameter of 15 mm, a circular glass filter with a diameter of 24 mm, and a separator with a diameter of 24 mm are laminated in this order in a metal fixture, and 0.1 mL of electrolyte is injected. Then, the negative electrode as the object is placed on the separator, the upper cover of the fixture is installed, and a metal label is assembled, thereby manufacturing a button battery.
[0217] <Measurement of Li doping amount>
[0218] In the present disclosure, the Li doping amount is a value obtained according to the following steps (1) to (4).
[0219] (1) After adjusting the non-aqueous lithium storage element to a voltage of 4.0 V, the outer package is removed in an argon box, and the negative electrode located at the 26th piece from the outermost layer of the electrode laminate is taken out.
[0220] (2) Using the taken-out negative electrode, a button-type negative electrode monopolar battery unit is manufactured according to the steps described in the above "Manufacture of button-type negative electrode monopolar battery unit".
[0221] (3) The battery unit is subjected to constant current charging to a voltage of 5.0 mV at a current value of 1.4 mA and constant voltage charging at a voltage of 5.0 mV in a constant temperature bath set at a temperature of 25 °C, and the total charging capacity at this time is set as Q1. In addition, constant voltage charging at a voltage of 5.0 mV is continued until the current value during the continuation of the constant voltage charging becomes less than 0.70 mA.
[0222] (4) Next, the battery unit is subjected to constant current discharge to a voltage of 2.5 V at a current value of 1.4 mA in a constant temperature bath set at 25 °C, and the discharge capacity at this time is set as Q2. At this time, the Li doping amount F [%] is as follows.
[0223] F = (Q2 - Q1) × 100 / Q2
[0224] <Measurement of Li inactivation rate>
[0225] In the present disclosure, the Li inactivation rate is a value obtained according to the following steps (1) to (5).
[0226] (1) Prepare two non-aqueous lithium storage elements manufactured by the same steps. For one of them, a high-temperature cycle test is performed using the method described in the above "High-temperature cycle test". For the other one, the charging capacity Q1 is calculated using the method described in the above "Measurement of Li doping amount".
[0227] (2) After the nonaqueous lithium storage device subjected to the high temperature cycle test was adjusted to a voltage of 4.0 V, the outer casing was removed in an argon box, and the negative electrode located at the 26th sheet from the outermost layer of the electrode stack was taken out.
[0228] (3) Using the removed negative electrode, a button-type negative electrode monopolar battery cell was produced according to the procedure described in the above-mentioned "Production of button-type negative electrode monopolar battery cell".
[0229] (4) The battery cell was charged at a constant current of 1.4 mA to a voltage of 5.0 mV and a constant voltage of 5.0 mV in a thermostatic chamber set at a temperature of 25°C, and the total charge capacity at this time was set to Q3. Furthermore, the constant voltage charge at a voltage of 5.0 mV was continued until the current value during the constant voltage charge was less than 0.70 mA.
[0230] (5) Next, the battery cell was discharged at a constant current of 1.4 mA to a voltage of 2.5 V in a thermostatic chamber set at 25°C, and the discharge capacity at this time was set to Q4. When the implementation time of the high temperature cycle test was set to T [hour], the Li deactivation rate D [% / h] after the high temperature cycle test was implemented 1 / 2 ] as shown below.
[0231] D=(Q3-Q1)×100 / (Q4×T 1 / 2 )
[0232] 《Example 1》
[0233] <Manufacturing of non-aqueous lithium storage element>
[0234] [Preparation of positive electrode active material]
[0235] The crushed coconut shell carbide was placed in a small carbonization furnace and carbonized at 500°C for 3 hours under a nitrogen atmosphere to obtain a carbide. The obtained carbide was placed in an activation furnace, and the steam heated in a preheating furnace was introduced into the activation furnace at 1 kg / h, and the temperature was raised to 900°C for 8 hours for activation. The activated carbide was taken out and cooled under a nitrogen atmosphere to obtain activated activated carbon. The obtained activated activated carbon was washed with water for 10 hours, and then the water was removed. After drying in an electric dryer maintained at 115°C for 10 hours, it was crushed in a ball mill for 1 hour to obtain activated carbon 1.
[0236] The average particle size of activated carbon 1 was measured using a laser diffraction particle size distribution measuring device (SALD-2000J) manufactured by Shimadzu Corporation, and the result was 5.5 μm. In addition, the pore distribution of activated carbon 1 was measured using a pore distribution measuring device (AUTOSORB-1AS-1-MP) manufactured by Yuasa Ionics. As a result, the BET specific surface area was 2360 m 2 / g, mesopore volume (V1) is 0.52cm 3 / g, micropore volume (V2) is 0.88cm 3 / g, V1 / V2=0.59.
[0237] [Manufacturing of positive electrode precursor]
[0238] Activated carbon 1, lithium carbonate, carbon black, acrylic latex, CMC (carboxymethyl cellulose), PVP (polyvinyl pyrrolidone), and distilled water with a solid content of 43.0% by mass were mixed, and the mixture was kneaded at 60 rpm using a kneading machine Hivis MIX manufactured by PRIMIX to obtain a positive electrode coating liquid 1. The positive electrode coating liquid 1 was applied to both sides of an aluminum foil having a thickness of 15 μm using a die coater manufactured by Toray Engineering Co., Ltd. at a coating speed of 1 m / s, and after drying at a drying temperature of 100° C., it was pressed using a roll press under a pressure of 4 kN / cm and a surface temperature of the pressing part of 25° C. to obtain a positive electrode precursor 1. The thickness of the positive electrode active material layer of the positive electrode precursor 1 was determined by subtracting the thickness of the aluminum foil from the average value of the thickness measured at any 10 locations of the positive electrode precursor 1 obtained above using a film thickness meter Linear Gauge Sensor GS-551 manufactured by Ono Keiki Co., Ltd. As a result, the thickness of the positive electrode active material layer of the positive electrode precursor 1 was 70 μm per one side.
[0239] [Manufacturing of negative electrode]
[0240] Artificial graphite, carbon black, CMC (carboxymethyl cellulose) and SBR (styrene-butadiene rubber) latex, and distilled water having a solid content of 34.0% by mass were mixed, and the mixture was kneaded at 60 rpm using a kneading machine Hivis MIX manufactured by PRIMIX to obtain a negative electrode coating liquid 1. The negative electrode coating liquid 1 was applied to one side and both sides of a copper foil having a thickness of 10 μm using a die coater manufactured by Toray Engineering Co., Ltd. at a coating speed of 1 m / s, and after drying at a drying temperature of 85° C., it was pressed using a roll press at a pressure of 4 kN / cm and a surface temperature of the pressing part of 25° C. to obtain a single-sided negative electrode 1 and a double-sided negative electrode 1. The thickness of the negative electrode active material layer of the negative electrode 1 was determined by subtracting the thickness of the copper foil from the average value of the thickness measured at any 10 locations of the double-sided negative electrode 1 obtained above using a film thickness meter Linear Gauge Sensor GS-551 manufactured by Ono Keiki Co., Ltd. As a result, the thickness of the negative electrode active material layer of the double-sided negative electrode 1 was 30 μm per one side.
[0241] [Example of Preparation of Electrolyte Solution]
[0242] A mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) was used as an organic solvent to dissolve the electrolyte salt in such a manner that the total concentration of LiPF6 and LiFSI became 1.2 mol / L. Vinyl sulfate (1,3,2-dioxathiolane-2,2-dioxide) was added as an additive to obtain a non-aqueous electrolyte solution 1.
[0243] [Fabrication of laminated negative electrode monopolar battery cell]
[0244] Cut the negative electrode active material layer of the single-sided negative electrode 1 in a size of 4.5 cm × 9.5 cm. Next, cut the copper foil in a size of 4.6 cm × 9.6 cm, overlap the metal lithium foil cut into a rectangular shape, and press the lithium foil to the copper foil with a hand roller to obtain a metal lithium counter electrode. Then, the metal lithium counter electrode, the glass filter, the separator, and the single-sided negative electrode 1 are stacked in sequence to obtain an electrode stack. The two negative terminals are ultrasonically welded to the obtained electrode stack, placed in a container formed by an aluminum laminate packaging material, and the three sides containing the electrode terminal portion are sealed by heat sealing. The electrode stack prepared in this way is used as a negative single-pole battery cell precursor 1.
[0245] [Injection of laminated negative electrode monopolar battery cell]
[0246] Under atmospheric pressure, in a dry air environment with a temperature of 25°C and a dew point of -40°C or less, about 6.0g of non-aqueous electrolyte 1 is injected into the outer body containing the negative electrode monopolar battery cell precursor 1 manufactured by the above method. Next, the outer body containing the electrode laminate and the non-aqueous electrolyte is placed in a decompression chamber, decompressed from atmospheric pressure to -87kPa, restored to atmospheric pressure, and left to stand for 5 minutes. After that, the process of decompressing the outer body in the chamber from atmospheric pressure to -87kPa and then returning to atmospheric pressure is repeated 4 times, and then left to stand at atmospheric pressure for 15 minutes. The non-aqueous electrolyte 1 is impregnated into the electrode laminate through the above process. Then, the electrode laminate impregnated with the non-aqueous electrolyte 1 is placed in a decompression sealing machine, and under a state of decompression to -95kPa, it is sealed at 180°C with a pressure of 0.1MPa for 10 seconds, thereby sealing the outer body. The battery cell made in this way is used as a negative electrode monopolar battery cell 1.
[0247] [Calculation of C ratio]
[0248] The negative electrode monopolar battery cell was charged and discharged by the method described in the above "C rate calculation method", and the C rate was calculated. As a result, Q was 0.40 Ah / g and G was 10 g. Therefore, in this disclosure, it was confirmed that 1 C is equivalent to 4.0 A.
[0249] [Assembly]
[0250] Cut the positive electrode precursor 1 into 25 pieces with a size of 8.4cm×11.0cm for the positive electrode active material layer. Then cut the double-sided negative electrode 1 into 26 pieces with a size of 8.8cm×11.2cm for the negative electrode active material layer, and prepare a polyethylene separator (manufactured by Asahi Kasei, thickness 20μm). Use a lamination machine manufactured by Hitachi Power Solutions to layer them in the order of double-sided negative electrode 1, separator, and positive electrode precursor in such a way that the outermost layer is the double-sided negative electrode 1 to obtain an electrode laminate. At this time, the lamination is performed in such a way that the separator becomes a zigzag shape. The positive terminal and the negative terminal are ultrasonically welded to the obtained electrode laminate, placed in a container formed by an aluminum laminate packaging material, and the three sides containing the electrode terminal portion are sealed by heat sealing.
[0251] [Liquid injection process]
[0252] In a dry air environment with a temperature of 25°C and a dew point below -40°C, about 70g of a non-aqueous electrolyte 1 with a liquid temperature of 25°C is injected into the electrode stack contained in the aluminum laminate packaging material. The electrode stack is then placed in a decompression chamber, and the operation of reducing pressure from normal pressure to -91kPa and then returning to atmospheric pressure is repeated 5 times. The electrode body is then taken out of the chamber and allowed to stand at atmospheric pressure for 5 minutes. The non-aqueous electrolyte is infiltrated into the electrode stack through the above steps. Next, the non-aqueous lithium storage element precursor is placed in a decompression sealing machine, and in a state where the pressure is reduced to -95kPa, it is sealed at 180°C with a pressure of 0.1MPa for 10 seconds, thereby sealing the aluminum laminate packaging material. The non-aqueous lithium storage element precursor 1 is thus made.
[0253] [Alkali metal doping process]
[0254] The obtained non-aqueous lithium storage element precursor 1 was charged at a constant current of 0.40 A at 45°C using a charge and discharge tester (ACD-10APS(01)) manufactured by Asuka Electronics Co., Ltd. until the voltage reached 4.2 V. Then, constant current charging was performed at a current of 1.3 A until the voltage reached 4.5 V, and then constant voltage charging was continued for 2.5 hours to perform alkali metal doping.
[0255] [Cyclic aging process]
[0256] The nonaqueous lithium storage element precursor 1 after the alkali metal doping step was discharged at a constant current of 6.0 A at a temperature of 45° C. until the voltage reached 2.0 V, and then discharged at a constant voltage of 2.0 V for 10 minutes. The following (1) and (2) were regarded as one cycle, and a total of 5 cycles were performed.
[0257] (1) Constant current charging was performed at a current value of 6.0 A until the voltage reached 4.5 V, and then constant voltage charging was performed at a voltage of 4.5 V for 10 minutes.
[0258] (2) The battery was discharged at a constant current of 6.0 A until the voltage reached 2.0 V, and then discharged at a constant voltage of 2.0 V for 10 minutes.
[0259] [Aging process]
[0260] After the cycle aging process, the non-aqueous lithium storage element precursor 1 is charged at a constant current of 10A at a temperature of 60°C until the voltage reaches 4.2V, and then charged at a constant voltage of 4.2V for 30 minutes to adjust the voltage to 4.2V. The non-aqueous lithium storage element precursor is then stored in a constant temperature bath at 60°C for 6 hours. The non-aqueous lithium storage element precursor 1 is then discharged at a constant current of 10A at a temperature of 60°C until the voltage reaches 2.0V, and then discharged at a constant voltage of 2.0V for 30 minutes to adjust the voltage to 2.0V. The non-aqueous lithium storage element precursor is then stored in a constant temperature bath at 60°C for 6 hours.
[0261] [Exhaust process]
[0262] For the aged non-aqueous lithium storage element precursor 1, a portion of the aluminum laminated packaging material is unsealed in a dry air environment at a temperature of 25°C and a dew point of -40°C. Next, the non-aqueous lithium storage element precursor is placed in a decompression chamber, and a diaphragm pump (N816.3KT.45.18) manufactured by KNF is used. It takes 3 minutes to reduce the pressure from atmospheric pressure to -80kPa, and then it takes 3 minutes to return to atmospheric pressure. This process is repeated a total of 3 times. The non-aqueous lithium storage element precursor is then placed in a decompression sealing machine, and after the pressure is reduced to -90kPa, it is sealed at 200°C with a pressure of 0.1MPa for 10 seconds, thereby sealing the aluminum laminated packaging material. The non-aqueous lithium storage element 1 is completed through the above process.
[0263] <Evaluation of non-aqueous lithium storage element>
[0264] [Acquisition and Binarization of SEM Images]
[0265] According to the steps described in the above-mentioned "SEM image acquisition method and binarization method", the SEM image of the non-aqueous lithium storage element 1 was acquired and binarized. The acquired SEM image and the binarized SEM image are shown in Figure 1 and Figure 2 In Example 1, it was confirmed that the portion with low brightness in the SEM image was finely distributed. When the portion with low brightness in the SEM image was magnified, the presence of a deposit containing a compound derived from metal Li was confirmed.
[0266] [Calculation of the area of the deposit]
[0267] The calculation was performed according to the steps described in the above "Calculation of the maximum area S and average area T of the dark field area", and the result was S = 2408 pixels. 2 , T = 277 pixels 2 .
[0268] [Determination of Li doping amount]
[0269] The Li doping amount of the nonaqueous lithium storage element was measured according to the procedure described in the above “Measurement of Li doping amount”. As a result, it was confirmed that the Li doping amount of the nonaqueous lithium storage element 1 was 93%.
[0270] [High temperature cycle test]
[0271] The high temperature cycle test was carried out according to the procedure described in the above-mentioned "High Temperature Cycle Test".
[0272] [Determination of Li deactivation rate]
[0273] The Li deactivation rate was measured according to the procedure described in the above-mentioned measurement of the Li deactivation rate. As a result, the Li deactivation rate of the non-aqueous lithium storage element 1 was 0.446% / h. 1 / 2 .
[0274] 《Example 2》
[0275] The non-aqueous lithium storage element 2 was prepared by the same method as in Example 1 except that the conditions of the alkali metal doping process were changed. In the alkali metal doping process of the non-aqueous lithium storage element 2, constant current charging was performed at a current value of 0.80A at 45°C until the voltage reached 4.2V, followed by constant current charging at a current value of 1.3A until the voltage reached 4.5V, and then constant voltage charging was continued for 2.5 hours. The deposit area, Li doping amount, and Li deactivation rate were then calculated using the same method as in Example 1. The calculation results are shown in Table 1.
[0276] 《Example 3》
[0277] The non-aqueous lithium storage element 3 was prepared by the same method as in Example 1 except that the conditions of the alkali metal doping process were changed. In the alkali metal doping process of the non-aqueous lithium storage element 3, constant current charging was performed at a current value of 0.20A at 45°C until the voltage reached 4.2V, followed by constant current charging at a current value of 1.3A until the voltage reached 4.5V, and then constant voltage charging was continued for 2.5 hours. Then, the deposit area, Li doping amount, and Li deactivation rate were calculated using the same method as in Example 1. The calculation results are shown in Table 1.
[0278] 《Example 4》
[0279] The non-aqueous lithium storage element 4 was prepared by the same method as in Example 1 except that the conditions of the alkali metal doping process were changed. In the alkali metal doping process of the non-aqueous lithium storage element 4, constant current charging was performed at a current value of 0.40A at 45°C until it reached 4.5V, and then constant voltage charging was continued for 2.5 hours. Then, the deposit area, Li doping amount, and Li deactivation rate were calculated by the same method as in Example 1. The calculation results are shown in Table 1.
[0280] 《Example 5》
[0281] The non-aqueous lithium storage element 5 was prepared by the same method as in Example 1 except that the conditions of the alkali metal doping process were changed. In the alkali metal doping process of the non-aqueous lithium storage element 5, constant current charging was performed at a current value of 0.20A at 45°C until it reached 4.5V, and then constant voltage charging was continued for 2.5 hours. Then, the deposit area, Li doping amount, and Li deactivation rate were calculated by the same method as in Example 1. The calculation results are shown in Table 1.
[0282] Comparative Example 1
[0283] The nonaqueous lithium storage element 6 was prepared in the same manner as in Example 1 except that the conditions of the alkali metal doping step were changed. In the alkali metal doping step of the nonaqueous lithium storage element 6, constant current charging was performed at a current value of 1.3 A at 45° C. until the voltage reached 4.5 V, and then mechanical constant voltage charging was performed for 2.5 hours.
[0284] Then, the SEM image was obtained by the same method as in Example 1. The obtained surface SEM image and the binarized SEM image are shown in Figure 3 and Figure 4 . In Comparative Example 1, it was confirmed that the portion with low brightness in the SEM image was distributed in an island shape. When the portion with low brightness in the SEM image was magnified, the presence of deposits derived from metal Li was confirmed in the same manner as in Example 1. Therefore, in the example, fine deposits were sparsely distributed, whereas in Comparative Example 1, coarse deposits were distributed in an island shape. Then, the deposit area, Li doping amount, and Li deactivation rate were calculated in the same manner as in Example 1. The calculation results are shown in Table 1.
[0285] 《Comparative Example 2》
[0286] The non-aqueous lithium storage element 7 was prepared by the same method as in Example 1 except that the conditions of the alkali metal doping process were changed. In the alkali metal doping process of the non-aqueous lithium storage element 7, constant current charging was performed at a current value of 1.3A at 45°C until the voltage reached 4.2V, and then constant current charging was performed at a current value of 0.4A until the voltage reached 4.5V, and then constant voltage charging was continued for 2.5 hours. Then, the deposit area, Li doping amount, and Li deactivation rate were calculated using the same method as in Example 1. The calculation results are shown in Table 1.
[0287] [Table 1]
[0288]
[0289] From the above, it was confirmed that the Li deactivation rate can be suppressed by reducing the area of the deposits formed on the negative electrode. In addition, since a larger Li doping amount can extend the life of the non-aqueous lithium storage element, the Li doping amount is more preferably 85% or more.
[0290] Industrial Applicability
[0291] The non-aqueous lithium storage element of the present invention can be used, for example, to make a storage module by connecting a plurality of non-aqueous lithium storage elements in series or in parallel. The non-aqueous lithium storage element and storage module of the present invention can be appropriately used in various storage systems, for example: a power regeneration system of a hybrid drive system of an automobile requiring high-load charge-discharge cycle characteristics; a power load balancing system in natural power generation such as solar power generation, wind power generation, or microgrids; an uninterruptible power supply system in a factory's production equipment, etc.; a non-contact power supply system for the purpose of balancing and storing voltage fluctuations such as microwave power transmission and electric field resonance; and an energy harvesting system for the purpose of using power generated by vibration power generation, etc.; electric vehicles, plug-in hybrid vehicles, electric bicycles, hub motor systems, and electric power steering systems as vehicle power sources; a fast charging system that charges with a large current in order to charge in a short time. The non-aqueous lithium storage element of the present invention can maximize the effect of the present invention when used, for example, as a lithium ion capacitor or a lithium ion secondary battery, and is therefore preferred.
Claims
1. A non-aqueous lithium storage element, comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte containing lithium ions, wherein the positive electrode has a positive electrode active material layer containing a positive electrode active material and an alkali metal compound, wherein: Regarding the negative electrode, a secondary electron image of the surface of the negative electrode active material layer obtained by taking a scanning electron microscope at a magnification of 100 times without being exposed to the atmosphere is binarized with the brightness of each pixel, and there are bright field areas and a plurality of dark field areas in the binarized image, and the plurality of dark field areas correspond to deposits formed on the surface of the negative electrode active material layer. When 1 pixel is set to 1.46 μm, the maximum value S [pixel] of the area occupied by each of the dark field areas 2 ] is less than 4000.
2. The nonaqueous lithium storage element according to claim 1, wherein The positive electrode active material is activated carbon, the alkali metal compound is lithium carbonate, and the non-aqueous electrolyte solution includes an electrolyte salt containing lithium ions and a cyclic compound selected from cyclic carbonates and cyclic sulfates.
3. The nonaqueous lithium storage element according to claim 1 or 2, wherein The maximum value S of the dark field area is 3500 [pixels 2 ]the following.
4. The nonaqueous lithium storage element according to claim 3, wherein The maximum value S of the area of the dark field region is 2408 [pixels 2 ] or more, 3000[pixels 2 ]the following.
5. The nonaqueous lithium storage element according to claim 4, wherein The non-aqueous electrolyte solution contains the cyclic sulfate ester, and the cyclic sulfate ester is vinyl sulfate.
6. The nonaqueous lithium storage element according to claim 1, wherein The deposits corresponding to the dark field region of the binary image of the surface of the negative electrode active material include a compound derived from metal Li.
7. The nonaqueous lithium storage element according to claim 1, wherein The doping amount of lithium ions in the negative electrode is greater than or equal to 85% and less than or equal to 100%.
8. The nonaqueous lithium storage element according to claim 1, wherein In the binarized image, when 1 pixel is set to 1.46 μm, the average value T [pixel] of the area occupied by each of the dark field regions is 2 ] is below 600.
9. The nonaqueous lithium storage element according to claim 8, wherein The average value T is 400 or less.
10. A method for producing a non-aqueous lithium storage element, wherein: The method comprises the following steps: A first doping step, charging a non-aqueous lithium storage element at 0.05C to 0.20C until it reaches 4.1V to 4.3V, wherein the non-aqueous lithium storage element comprises a positive electrode precursor, a negative electrode, a separator, and a non-aqueous electrolyte, wherein the positive electrode precursor comprises a positive electrode active material layer comprising a positive electrode active material and lithium carbonate, wherein the positive electrode active material comprises activated carbon, and the non-aqueous electrolyte comprises an electrolyte salt containing lithium ions and a cyclic compound selected from cyclic carbonates and cyclic sulfates; and In the second doping step, the nonaqueous lithium storage element is then charged at 0.25C to 1.0C until the voltage reaches 4.4V to 4.6V.
Citation Information
Patent Citations
Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
JP2021158088A
Power conversion device and washing machine including the same
JP2022143057A
Nonaqueous electrolyte secondary battery positive electrode and nonaqueous electrolyte secondary battery
WO2019244282A1
Non-aqueous lithium power storage element
WO2021066174A1